Electrolytic methods utilizing carbon dioxide and high nickel content anodes to produce desired nanocarbon allotropes
Patent Information
- Application Number
- JP2024529565
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-01-18
- Filing Date
- 2022-11-23
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2042-11-23
AI Technical Summary
Existing methods for producing carbon nanomaterials, such as chemical vapor deposition (CVD), are expensive and have a high carbon footprint, while electrolytic processes using lithium-carbonate electrolytes result in products with varying physical forms and properties due to different operating parameters.
A method and apparatus utilizing carbon dioxide (CO2) in molten carbonate electrolysis with controlled electrolysis parameters, including anode and cathode compositions, additives, and current densities to produce carbon nanomaterials with high purity and specific allotropes like carbon nanotubes, nanobamboo, and nanopearl carbon.
Enables the production of carbon nanomaterials with high purity and controlled morphology, reducing production costs and environmental impact by leveraging CO2 as a reactant, and offering unique properties such as high strength, electrical conductivity, and thermal properties.
Smart Images

Figure 00000000_0000_ABST
Abstract
Description
[Technical field]
[0001]
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS This application claims priority to U.S. Provisional Patent Application No. 63 / 282,985, filed November 24, 2021, and U.S. Provisional Patent Application No. 63 / 300,499, filed January 18, 2022, the disclosures of each of which are incorporated herein by reference in their entireties.
[0002]
[0002] The present disclosure relates generally to the production of carbon nanomaterials. In particular, the present disclosure relates to methods and apparatus for producing carbon nanomaterials of various allotropes using electrolysis. [Background technology]
[0003]
[0003] Carbon nanotubes (CNTs) have the highest measured tensile strength of any material (strength 93,900 MPa). Multi-walled CNTs consist of concentric walls of cylindrical graphene sheets. Graphene is a sp 2 It is a two-dimensional honeycomb-structured material formed by a single layer of hybrid orbital carbon atoms. Graphite, nanotubes, and fullerenes can be formed by graphene, for example, by rolling and stacking.
[0004]
[0004] Carbon nanomaterials (CNMs), including graphene structures, have many useful properties, including high strength, high electrical conductivity, high thermal conductivity, durability, hardness, flexibility, lubricity, they can also be used as catalysts, and can be chemically modified. These useful properties mean that applications of CNTs are steadily growing. For example, low (typically <<1%) concentrations of CNTs in structural materials can increase the strength of a range of structural materials, such as cement, steel, plastics, wood, and aluminum. Since each of these materials can have a high carbon footprint, carbon composites with increased strength or other useful properties that require no, little, or little of the high footprint material could dramatically lower the carbon footprint. Other applications that utilize the useful properties of carbon nanomaterials include: cables or wires, electric vehicles, athletic equipment, medical applications, electronics, batteries, supercapacitors, sensors, plastics, polymers, textiles, hydrogen storage, and water treatment.
[0005]
[0005] A known process by which CNTs are produced is chemical vapor deposition (CVD). However, CVD of CNTs is expensive - current estimates are at costs between $100K and $600K per ton of CNTs produced, and CVD has a high carbon footprint. Summary of the Invention [Problem to be solved by the invention]
[0006]
[0006] In addition to chemical vapor deposition (CVD), electrolytic reactions using carbon dioxide (CO2) and lithium-carbonate electrolytes are also known processes for making CNTs. These electrolytic reactions may use electrolytic potentials of less than 1 volt to decompose CO2 in molten lithium-carbonate solutions to produce uniform CNT and carbon nanofiber (CNF) products with high coulombic efficiency. CO2 is extracted from the atmosphere with isotopes ( 13C) can be directly converted to CNTs, as confirmed by tracing. Electrolytic separation of CO2 in molten lithium-carbonate can occur as direct carbon capture and as conversion from air without CO2 preconcentration or with flue gas CO2 or with concentrated CO2. However, the products of known electrolytic reactions may contain different components in different physical forms, also called nanostructures, morphologies, or allotropes. Furthermore, products made with similar electrolyte operating parameters can result in different physical forms and different associated properties of the different physical forms. [Means for solving the problem]
[0007]
[0007] The embodiments of the present disclosure relate to methods and apparatus for producing carbon nanomaterial products (CNMs) containing various carbon allotropes, such as carbon nanotubes (CNTs), graphitic carbon, nanobamboo, conical carbon nanofibers, nanopearl carbon, coated CNTs, nano-onions, hollow nano-onions, nano-flowers, nano-dragons, branch and trunk CNTs (nantrees), nano-belts, nano-rods, long and / or straight CNTs, high aspect ratio CNTs, thin CNTs, and macroscopic assemblies of CNTs that are closely packed, including straight CNTs, nano-sponges, and nano-webs. The methods and apparatus use carbon dioxide (CO2) as a reactant in an electrolysis reaction to create these various carbon nanomaterials (CNMs). The embodiments of the present disclosure provide a wide range of controlled electrolysis methods and apparatuses of the present disclosure to selectively provide CNM products with high purity of one or more of the desired allotropes.
[0008] Some embodiments of the present disclosure relate to a method for making a CNM product, the method including: heating a carbonate electrolyte to obtain a molten carbonate electrolyte, positioning the molten carbonate electrolyte between an anode and a cathode in an electrolytic cell, applying a current to the cathode and the anode in the electrolytic cell, and selecting one or more of the following operating parameters: cathode composition or configuration, anode composition or configuration, additives to be added to the electrolyte, aging the electrolyte, current density, upward change (increase or decrease) in current density, time for applying the current such that the CNM product contains a higher relative amount of the desired allotrope. Examples of desired allotropes include, but are not limited to: carbon nanotubes (CNTs), graphitic carbon, nanobamboo, conical carbon nanofibers, nanopearl carbon, coated CNTs, nano-onions, hollow nano-onions, nanoflowers, nanodragons, branch and trunk CNTs (nantrees), nanobelts, nanorods, long and / or straight CNTs, high aspect ratio CNTs, thin CNTs, macroscopic assemblies of CNTs, or combinations thereof. The method further includes collecting the CNM product from the cathode.
[0009]
[0009] Methods and apparatus use carbon dioxide (CO2) as a reactant in an electrolysis reaction to create various carbon allotropes. The disclosed embodiments provide a wide variety of controlled electrolysis methods and apparatuses to selectively provide CNM products having one or more of these allotropes in high purity. In the absence of sufficient CO2, the carbonate electrolyte becomes the source of carbon and is consumed. The CO2 can come from an external gas, or if there is temporarily insufficient external CO2 to support the desired electrolysis reaction, the source of carbon can come from carbonate decomposition. Without being bound by any theory, carbonate decomposition is believed to result in the production of CO2 and O 2 and other oxides and CO3 2- In the latter case, this oxide build-up acts as a reserve to scavenge excess CO2 when it becomes available.
[0010] In some embodiments of the present disclosure, the method may be modified to dope a CNM product with a desired allotrope therein. The doped allotrope has atoms of the doping component directly incorporated within the chemical structure of the doped allotrope, thereby imparting new or enhanced physical and / or chemical properties to the doped allotrope when compared to the undoped allotrope.
[0011] In some embodiments of the present disclosure, the method may be modified to create a CNM product that is responsive to an external magnetic field and includes a desired allotrope therein. The magnetic allotrope may incorporate atoms of a magnetic material therein using chemical addition and / or carbide-facilitated mechanisms, such that the magnetic allotrope is capable of moving along a magnetic field when located at or near a source of the magnetic field.
[0012]
[0012] Without wishing to be bound by any particular theory, some embodiments of the present disclosure provide a new method to synthesize new allotropes of carbon by molten carbonate electrolysis using the greenhouse gas CO2 as a reactant. A vast array of unique nanocarbon structures exists and has been discovered beyond the traditional world of diamond, graphite, and buckyballs. Until recently, CO2 was thought to be unreactive. Herein, we show that CO2 can be converted into distinct nanobamboo, nanopearl, nanodragon, solid and hollow nanoonion, nanotree, nanorod, nanobelt, and nanoflower allotropes of carbon, among others. The ability to generate these allotropes in high purity by simple electrolysis - analogous to the decomposition of aluminum oxide to generate aluminum, but instead by the decomposition of carbon dioxide to generate nanocarbon - opens up an array of inexpensive unique materials with the potential to provide new properties of high strength, new electrical properties, new thermal properties, new flexibility, new charge storage properties, new lubricity, and new robustness. The commercial production technique for nanocarbons is chemical vapor deposition (CVD), which is 10-100 times more expensive, and generally requires metal-organic reactants and has a highly positive rather than carbon-negative carbon footprint. Various nanocarbon allotropes were electrochemically prepared by varying anode and cathode compositions and configurations, electrolyte compositions, pre-electrolysis treatments (aging), and current ramps and current densities.
[0013] Some embodiments of the present disclosure relate to a first method for producing a CNM product, the method comprising: heating an electrolyte medium to obtain a molten electrolyte medium, positioning the molten electrolyte medium between a high nickel content anode and a cathode of an electrolytic cell, introducing a source of carbon into the electrolytic cell, applying an electric current to the cathode and the anode of the electrolytic cell, and collecting the CNM product from the cathode. In these embodiments of the first method, the CNM product comprises a minimum relative amount of at least 70% by weight compared to the total weight of the CNM product of a desired allotrope selected from the group of carbon nanotubes (CNTs) of a desired length, curled CNTs, cone-shaped carbon nanofibers, nanobamboos, hollow nano-onions, and nanotrees.
[0014] Some embodiments of the present disclosure relate to a first method, in which the anode is made of substantially pure nickel, the cathode includes copper, the desired allotrope is CNT of a desired length, and the desired length is between about 30 μm and about 60 μm.
[0015] Some embodiments of the present disclosure relate to a first method, wherein the first method further comprises adding an iron-containing salt to the electrolyte medium or the molten electrolyte medium.
[0016] In some embodiments of the present disclosure, the iron-containing salt is added in an amount between about 0.01% and about 5% by weight relative to the amount of electrolyte medium or molten electrolyte medium, the anode is made of Nichrome C, and the current is about 0.1 A / cm 2 ~about 0.2A / cm 2 and wherein the desired allotrope is a CNT of a desired length, the desired length being between about 50 μm and about 100 μm.
[0017]
[0017] Some embodiments of the present disclosure relate to a first method, in which an iron-containing salt is added in an amount between about 0.01% by weight and about 5% by weight relative to the amount of electrolyte medium or molten electrolyte medium, the anode is made of Nichrome A, the desired allotrope is CNT of a desired length, and the desired length is between about 20 μm and about 80 μm.
[0018] Some embodiments of the present disclosure include a method for producing a galvanic electrolytic cell comprising the steps of: adding an iron-containing salt in an amount between about 0.01% and about 5% by weight based on the amount of electrolyte medium or molten electrolyte medium; forming an anode from Nichrome C; and applying a current of about 0.1 A / cm 2 ~about 0.2A / cm 2 and wherein the desired allotrope is a CNT of a desired length, the desired length being between about 10 μm and about 30 μm.
[0019] In some embodiments of the present disclosure, the iron-containing salt is added in an amount between about 0.01% and about 5% by weight based on the amount of electrolyte medium or molten electrolyte medium, the anode is made of Nichrome C, and the current is about 0.1 A / cm 2 ~about 0.75A / cm 2 and the desired allotrope is a CNT of a desired length, the desired length being between about 100 μm and about 200 μm.
[0020] In some embodiments of the present disclosure, the iron-containing salt is added in an amount between about 0.01% and about 5% by weight based on the amount of electrolyte medium or molten electrolyte medium, the anode is made of Nichrome C, and the current is about 0.05 A / cm 2 ~about 0.2A / cm 2 and the desired allotrope is a CNT of a desired length, the desired length being between about 30 μm and about 60 μm.
[0021]
[0021] Some embodiments of the present disclosure relate to a first method, in which an iron-containing salt is added in an amount between about 0.01% by weight and about 1% by weight relative to the amount of electrolyte medium or molten electrolyte medium, the anode is made of nichrome C, the desired allotrope is a mixture of CNTs and curled CNTs, and the relative amount of curled CNTs is at least 25% by weight of the total weight of the CNM product.
[0022]
[0022] Some embodiments of the present disclosure relate to a first method, in which an iron-containing salt is added in an amount of about 0.01% by weight to about 5% by weight relative to the amount of electrolyte medium or molten electrolyte medium, the anode is a composite anode comprising a first layer of Inconel 625 and at least a second layer of Inconel 600, and the desired allotrope is a CNT of a desired length, the desired length being between about 10 μm and about 100 μm.
[0023]
[0023] Some embodiments of the present disclosure relate to a first method, in which an iron-containing salt is added in an amount between about 0.01 weight % and about 5 weight % relative to the amount of electrolyte medium or molten electrolyte medium, the anode is a composite anode including a first layer of a first Inconel alloy and at least a second layer of a second Inconel alloy, the desired allotrope is a CNT of a desired length, and the desired length is between about 100 μm and about 500 μm.
[0024]
[0024] Some embodiments of the present disclosure relate to a first method, in which an iron-containing salt is added in an amount of about 0.01% by weight to about 5% by weight relative to the amount of electrolyte medium or molten electrolyte medium, and further comprising a step of adding between about 0.01% by weight to about 5% by weight of a nickel-containing additive to the electrolyte medium, and the desired allotrope is curled CNT.
[0025] Some embodiments of the present disclosure relate to a first method, in which the anode is an Inconel alloy.
[0026] Some embodiments of the present disclosure relate to a first method, in which the anode is a composite anode including a first layer of a first Inconel alloy and at least a second layer of a second Inconel alloy.
[0027] Some embodiments of the present disclosure relate to a first method, in which the anode and cathode are both made of substantially pure nickel and the desired allotrope is a mixture of nanobamboo and carbon nanotubes.
[0028]
[0028] Some embodiments of the present disclosure relate to a first method, further comprising the step of adding a nickel-containing additive to the electrolyte medium or the molten electrolyte medium relative to the amount of the electrolyte medium or the molten electrolyte medium, wherein the anode is a composite anode comprising a first layer of Inconel 718 and at least a second layer of Inconel 600, and the desired allotrope is nanobamboo.
[0029] Some embodiments of the present disclosure relate to a first method, in which the molten electrolyte is freshly melted and the CNM product further comprises conical nanotube allotropes.
[0030]
[0030] Some embodiments of the present disclosure relate to a first method, further comprising a step of adding a nickel-containing additive to the electrolyte medium or molten electrolyte medium, wherein the anode is a composite anode comprising a first layer of Inconel 718 and at least a second layer of Inconel 600, and the desired allotrope is nanobamboo.
[0031]
[0031] Some embodiments of the present disclosure relate to a first method, further comprising a step of introducing a lithium-containing additive into the electrolyte medium or molten electrolyte medium, wherein the anode is a composite anode comprising a first layer of Inconel 718 and at least a second layer of Inconel 600, and the desired allotrope is nanotrees.
[0032] Some embodiments of the present disclosure relate to a first method, in which the lithium-containing additive is lithium oxide and is added in an amount between about 0.05% and 0.5% by weight relative to the amount of electrolyte medium or molten electrolyte medium.
[0033] Some embodiments of the present disclosure further include adding a nickel-containing additive to the electrolyte medium or molten electrolyte medium, the anode is made of Nichrome C, and the current is about 0.05 A / cm 2 ~0.12A / cm 2 and the desired allotrope is a hollow nano-onion CNR.
[0034]
[0034] Some embodiments of the present disclosure relate to a first method, further comprising the step of introducing a magnetic additive component into the electrolytic cell, the magnetic additive component comprising a magnetic material additive component, a carbide growth component, or any combination thereof, and wherein the desired allotrope is magnetic and moves when in a magnetic field.
[0035]
[0035] Some embodiments of the present disclosure relate to a first method which further includes a step of introducing a doped additive component into the electrolytic cell, wherein the desired allotrope is doped and atoms of the doped additive component are incorporated directly throughout the doped desired allotrope to impart desired physical and / or chemical properties to the doped desired allotrope that differ from the undoped desired allotrope.
[0036] Some embodiments of the present disclosure relate to a first CNM comprising a nanobamboo, the nanobamboo comprising multiple graphene layers positioned between a pair of bamboo knobs.
[0037] In these embodiments of the first CNM, the nanobamboo has an I of at least 1 as measured by Raman spectroscopy. D / I G The ratio is:
[0038] Some embodiments of the present disclosure relate to a second CNM that includes a nanotree, the nanotree including a trunk CNT having a plurality of branch CNTs extending away from the trunk CNT.
[0039] In these embodiments of the second CNM, the nanotrees have an I of between about 0.7 and about 0.9 as measured by Raman spectroscopy. D / I G The ratio is:
[0040]
[0040] In these embodiments of the second CNM, the second CNM further includes a curved graphene layer located proximate to each intersection of the multiple branch CNTs and trunk CNT.
[0041] Some embodiments of the present disclosure relate to a third CNM that includes one or more of high aspect ratio carbon nanotubes (CNTs) having an aspect ratio greater than 1000, nanobamboos; conical CNTs; curled CNTs, curled carbon nanofibers, or nanotrees.
[0042] Some embodiments of the present disclosure relate to a fourth CNM that includes a hollow nano-onion that defines an inner core.
[0043] In these embodiments of the fourth CNM, the inner core can be substantially empty.
[0044] In these embodiments of the fourth CNM, the inner core can contain a metal, where the metal is iron, nickel, or a combination thereof.
[0045] In these embodiments of the fourth CNM, the hollow nano-onion has an I of between about 0.2 and about 0.4 as measured by Raman spectroscopy. D / I G The ratio is:
[0046]
[0046] Some embodiments of the present disclosure relate to the use of a desired nanocarbon allotrope in one or more of a medical device, a structural enhancing additive, a strength enhancing additive, an electrical conductivity enhancing additive, a thermal conductivity enhancing additive, or a flexibility enhancing additive, a hardness enhancing additive, a durability enhancing additive, a lubrication enhancing additive, or as a catalyst, an electric vehicle, a cable or wire, an athletic equipment, a pharmaceutical delivery system, an electronics, a battery, a supercapacitor, a sensor, a plastic, a polymer, a textile, a hydrogen storage system, a light absorption enhancer for a surface, an electromagnetic shielding enhancer for a surface, a surface treatment, a surface coating, a paint, or a water treatment system, wherein the desired allotrope is selected from the group of carbon nanotubes (CNTs) of a desired length, curled CNTs, conical carbon nanofibers, nanobamboos, hollow nano-onions, and nanotrees.
[0047] Some embodiments of the present disclosure relate to a second method for producing a macroassembly product, the second method comprising: heating an electrolyte medium to obtain a molten electrolyte medium, positioning the molten electrolyte medium between an anode and a cathode of an electrolysis cell, introducing a source of carbon into the electrolysis cell, applying an electric current to the cathode and the anode of the electrolysis cell, and collecting the CNM product from the cathode. In an embodiment relating to the second method, the CNM product comprises a macroassembly product comprising a minimal relative amount of nanosponges, closely packed substantially parallel carbon nanotubes (CNTs), or nanowebs of CNTs.
[0048]
[0100] Some embodiments of the present disclosure relate to a second method, in which the anode and cathode are each made of a high nickel content material, and the CNM product comprises a nanosponge, with a minimum relative amount being at least 70% of the total weight of the CNM product.
[0049]
[0101] Some embodiments of the present disclosure relate to a second method in which current is applied in a first stage of increasing current density and a second stage of higher, substantially constant current density.
[0050]
[0102] Some embodiments of the present disclosure provide for a current density of about 0.005 A / cm for about 20 minutes during the second stage. 2 ~about 0.07A / cm 2 The second method relates to increasing the
[0051]
[0103] Some embodiments of the present disclosure provide a current density of approximately 0.1 A / cm 2 ~0.3A / cm 2 The present invention relates to a second method, which is between
[0052]
[0104] Some embodiments of the present disclosure relate to a second method, further comprising adding a nickel-containing additive to the electrolyte medium or the molten electrolyte medium.
[0053]
[0105] Some embodiments of the present disclosure relate to a second method, in which the nickel-containing additive is added in an amount between about 0.5% and about 0.2% by weight based on the amount of electrolyte medium or molten electrolyte medium.
[0054]
[0106] Some embodiments of the present disclosure relate to a second method, wherein the high nickel content material is a nichrome alloy.
[0055]
[0107] Some embodiments of the present disclosure relate to a second method, in which the anode is made of a high nickel content material and the CNM product comprises a nanoweb of CNTs.
[0056]
[0108] Some embodiments of the present disclosure are directed to a second method, in which the cathode comprises copper.
[0057]
[0109] Some embodiments of the present disclosure relate to a second method, further comprising adding a nickel-containing additive to the electrolyte medium or the molten electrolyte medium.
[0058]
[0110] Some embodiments of the present disclosure relate to a second method, in which the nickel-containing additive is added in an amount between about 0.5% and about 2% by weight based on the amount of electrolyte medium or molten electrolyte medium.
[0059]
[0111] In some embodiments of the present disclosure, the current is about 0.1 to 0.5 A / cm 2 A second method relates to a current density between 0.01 and 0.15.
[0060]
[0112] Some embodiments of the present disclosure are suitable for use with a current density of 0.2 A / cm 2 This relates to a second method,
[0061]
[0113] Some embodiments of the present disclosure relate to a second method, further comprising adding an iron-containing additive to the molten electrolyte, wherein the anode is a composite anode.
[0062]
[0114] Some embodiments of the present disclosure relate to a second method, in which the iron-containing additive is added in an amount of about 0.5% to about 2% by weight based on the amount of electrolyte medium or molten electrolyte medium.
[0063]
[0115] Some embodiments of the present disclosure relate to a second method, in which the composite anode includes a first layer of a first Inconel alloy and at least a second layer of a second Inconel alloy, and the CNM product includes close-packed, substantially parallel CNTs.
[0064]
[0116] Some embodiments of the present disclosure relate to a second method, in which the composite anode comprises a first layer of a nichrome alloy and at least a second layer of an Inconel alloy, the desired allotrope is CNT of a desired length, and the CNM product comprises closely packed, substantially parallel CNTs.
[0065]
[0117] Some embodiments of the present disclosure relate to a second method, further comprising introducing a magnetic additive component into the electrolytic cell, the magnetic additive component comprising a magnetic material additive component, a carbide growth component, or any combination thereof, and wherein the macro-assembly product is magnetic and moves when in a magnetic field.
[0066]
[0118] Some embodiments of the present disclosure relate to a second method further comprising introducing a doped additive component into the electrolytic cell, wherein the macroassembly product is doped and atoms of the doped additive component are directly incorporated throughout the doped macroassembly product to impart desired physical and / or chemical properties to the doped macroassembly product that differ from the undoped macroassembly product.
[0067]
[0119] Some embodiments of the present disclosure relate to a first macroassembly that includes a nanosponge defining pores having a size between about 50 nm and about 300 nm.
[0068]
[0120] Some embodiments of the present disclosure relate to a second macroassembly that includes a macroassembly that includes a nanosponge defining pores with sizes between about 100 nm and about 500 nm.
[0069]
[0121] Some embodiments of the present disclosure provide nanosponges with an I of between about 0.6 and about 0.8 as measured by Raman spectroscopy. D / I G The first (or second) macroassembly has a ratio:
[0070]
[0122] Some embodiments of the present disclosure relate to a third macroassembly that includes a nanoweb that defines pores having sizes between about 200 nm and about 1 μm.
[0071]
[0123] Some embodiments of the present disclosure include a nanoweb having an I of between about 0.2 and about 0.4 as measured by Raman spectroscopy. D / I G The third macroassembly has a ratio:
[0072]
[0124] Some embodiments of the present disclosure relate to a fourth macroassembly that includes a multiplicity of closely packed, substantially parallel CNTs that define an inter-CNT spacing of between about 50 nm and about 300 nm.
[0073]
[0125] Some embodiments of the present disclosure provide a method for manufacturing a carbon nanotube (CNT) having a large number of closely packed, substantially parallel CNTs with an I of between about 0.4 and about 0.6 as measured by Raman spectroscopy. D / I G The fourth macroassembly has a ratio:
[0074]
[0126] Some embodiments of the present disclosure relate to the use of the first or second or third macroassembly for nanofiltration.
[0075] Some embodiments of the present disclosure relate to the use of the fourth macro assembly for nanofiltration or as a conductive wire in an artificial neural net.
[0076] Some embodiments of the present disclosure relate to a third method for producing a CNM product, the method comprising: heating an electrolyte medium to obtain a molten electrolyte medium, positioning the molten electrolyte medium between a high nickel content anode and a copper-containing cathode of an electrolytic cell, introducing a source of carbon into the electrolytic cell, introducing an iron-containing salt into the electrolyte medium or the molten electrolyte medium, applying a low current density current to the cathode and anode of the electrolytic cell, and collecting the CNM product from the cathode. In these embodiments of the third method, the CNM product comprises a minimum relative amount of the desired allotrope, which is carbon nanodragons or carbon nanobelts.
[0077]
[0100] Some embodiments of the present disclosure relate to a third method, in which the iron-containing salt is added in an amount between about 0.05% and about 2% by weight relative to the amount of electrolyte medium or molten electrolyte medium.
[0078]
[0101] Some embodiments of the present disclosure relate to a third method, wherein the iron-containing salt is iron oxide.
[0079]
[0102] Some embodiments of the present disclosure are directed to a third method in which the anode is an Inconel alloy.
[0080]
[0103] In some embodiments of the present disclosure, the low current density current is about 0.3 A / cm 2 ~about 0.75A / cm 2 and wherein the desired allotrope is Nanodragon and the minimum relative amount is at least 70 wt % of the total weight of the CNM product.
[0081]
[0104] Some embodiments of the present disclosure relate to a third method, in which the copper-containing cathode is a Monel alloy.
[0082]
[0105] Some embodiments of the present disclosure relate to a third method, in which a low current density current is applied for about 4 hours.
[0083] Some embodiments of the present disclosure further include aging the molten electrolyte medium for at least 24 hours, wherein iron oxide is added prior to the aging step, and the low current density current is about 0.05 A / cm 2 ~0.15A / cm 2 and wherein the desired allotropes are nanobelts and the minimum relative amount is at least 90 wt % of the total weight of the CNM product.
[0084] Some embodiments of the present disclosure relate to a third method, in which the copper-containing cathode comprises Muntz brass.
[0085]
[0108] Some embodiments of the present disclosure relate to a third method, in which the low current density current is applied for between about 15 hours and about 20 hours.
[0086]
[0109] Some embodiments of the present disclosure relate to a third method, further comprising introducing a magnetic additive component into the electrolytic cell, wherein the magnetic additive component comprises a magnetic material additive component, a carbide growth component, or any combination thereof, and wherein the desired allotrope is magnetic and migrates when in a magnetic field.
[0087]
[0110] Some embodiments of the present disclosure relate to a third method, which further includes a step of introducing a doped additive component into the electrolytic cell, wherein the desired allotrope is doped and atoms of the doped additive component are incorporated directly throughout the doped desired allotrope to impart desired physical and / or chemical properties to the doped desired allotrope that differ from the undoped desired allotrope.
[0088]
[0111] Some embodiments of the present disclosure relate to a fifth CNM that includes a nanodragon, the nanodragon having an elongated body CNT with at least one protrusion extending away from the elongated body CNT.
[0089] Some embodiments of the present disclosure relate to a fifth CNM, wherein at least one protrusion is a multiple protrusion.
[0090] Some embodiments of the present disclosure relate to a fifth CNM, wherein each of the at least one protrusion comprises a branched CNT, a nodule of metallic growth, or any combination thereof.
[0091]
[0114] In some embodiments of the present disclosure, the Nanodragon has an I of between about 0.6 and about 0.8 as measured by Raman spectroscopy. D / I G The fifth CNM has a ratio.
[0092] Some embodiments of the present disclosure have an I of about 0.67 as measured by Raman spectroscopy.D / I G The sixth CNM comprises nanobelts having a ratio.
[0093] Some embodiments of the present disclosure relate to the use of a desired nanocarbon allotrope in one or more of a medical device, a structural enhancing additive, a strength enhancing additive, an electrical conductivity enhancing additive, a thermal conductivity enhancing additive, a flexibility enhancing additive, a hardness enhancing additive, a durability enhancing additive, a lubrication enhancing additive, or as a catalyst, an electric vehicle, a cable or wire, an athletic equipment, a drug delivery system, an electronics, a battery, a supercapacitor, a sensor, a plastic, a polymer, a textile, a hydrogen storage system, a light absorption enhancement of a surface, an electromagnetic shielding enhancement of a surface, a surface treatment, a surface coating, a paint, or a water treatment system, wherein the desired allotrope is a carbon nanodragon or a carbon nanobelt.
[0094] Some embodiments of the present disclosure relate to a fourth method for producing a CNM product, the fourth method comprising: heating an electrolyte medium to obtain a molten electrolyte medium, positioning the molten electrolyte medium between an anode and a cathode of an electrolytic cell, introducing a source of carbon into the electrolytic cell, introducing an iron-free additive into the electrolyte medium or the molten electrolyte medium, applying an electric current to the cathode and anode of the electrolytic cell, and collecting the CNM product from the cathode. In these embodiments of the fourth method, the CNM product comprises a minimum relative amount of a desired allotrope selected from the group of thin carbon nanotubes (CNTs), nanobamboos, nanorods, nanoonions, and nanoflowers.
[0095]
[0118] Some embodiments of the present disclosure relate to a fourth method, wherein the anode is a corrosion-resistant anode.
[0096]
[0119] Some embodiments of the present disclosure are directed to a fourth method, in which the corrosion-resistant anode comprises a precious metal.
[0097]
[0120] In some embodiments of the present disclosure, the current is about 0.05 A / cm2 ~0.15A / cm 2 A fourth method has a current density between
[0098]
[0121] Some embodiments of the present disclosure relate to a fourth method, in which the iron-free additive is a chromium-containing additive and is added in an amount between about 0.05% by weight and about 2% by weight relative to the amount of electrolyte medium or molten electrolyte medium, and the desired allotrope is a thin CNT having a length between about 25 μm and about 125 μm, with a minimum relative amount being greater than 70% relative to the total weight of the CNM product.
[0099]
[0122] Some embodiments of the present disclosure are directed to a fourth method, in which the cathode comprises a Monel alloy.
[0100]
[0123] Some embodiments of the present disclosure relate to a fourth method, in which the iron-free additive is a nickel-containing additive and is added in an amount between about 0.05% by weight and about 2% by weight relative to the amount of electrolyte medium or molten electrolyte medium, the desired allotropes are nanorods, and the minimum relative amount is greater than 70% relative to the total weight of the CNM product.
[0101]
[0124] Some embodiments of the present disclosure are directed to a fourth method, in which the cathode comprises a Monel alloy.
[0102]
[0125] Some embodiments of the present disclosure relate to a fourth method, in which the molten electrolyte medium is freshly melted.
[0103]
[0126] Some embodiments of the present disclosure relate to a fourth method, wherein the step of applying a current is caused for between 15 and 25 hours.
[0104]
[0127] Some embodiments of the present disclosure relate to a fourth method, wherein the iron-free additive is a nickel-containing additive and a chromium-containing additive, each of which is added in an amount between about 0.05% and about 2% by weight based on the amount of electrolyte medium or molten electrolyte medium, and the desired allotrope is nanobamboo, in a minimum relative amount between about 50% and about 80% by weight based on the total weight of the CNM product.
[0105]
[0128] Some embodiments of the present disclosure are directed to a fourth method, in which the cathode comprises Muntz brass.
[0106]
[0129] Some embodiments of the present disclosure relate to a fourth method, wherein the non-iron-containing additive is a lithium-containing additive and is added in an amount between about 1% and about 10% by weight based on the amount of electrolyte medium or molten electrolyte medium, and the desired allotrope is nano-onion, with a minimum relative amount between about 70% and about 99% by weight based on the total weight of the CNM product.
[0107]
[0130] Some embodiments of the present disclosure relate to a fourth method, wherein the lithium-containing additive is lithium phosphate.
[0108]
[0131] Some embodiments of the present disclosure are directed to a fourth method, in which the anode comprises a nichrome alloy.
[0109]
[0132] Some embodiments of the present disclosure are directed to a fourth method, in which the cathode comprises copper.
[0110]
[0133] Some embodiments of the present disclosure relate to a fourth method, wherein the iron-free additive is a cobalt-containing additive and is added in an amount of about 0.01% to about 5% by weight based on the amount of electrolyte medium or molten electrolyte medium, and the desired allotrope is nanoflower, with a minimum relative amount between about 70% to about 99% by weight based on the total weight of the CNM product.
[0111]
[0134] Some embodiments of the present disclosure relate to a fourth method, in which the cobalt-containing additive is cobalt powder and the molten electrolyte is aged.
[0112]
[0135] Some embodiments of the present disclosure are directed to a fourth method, in which the anode comprises a nichrome alloy.
[0113]
[0136] Some embodiments of the present disclosure are directed to a fourth method, in which the cathode comprises copper.
[0114]
[0137] Some embodiments of the present disclosure relate to a fourth method, further comprising introducing a magnetic additive component into the electrolytic cell, the magnetic additive component comprising a magnetic material additive component, a carbide growth component, or any combination thereof, and wherein the desired allotrope is magnetic and moves when in a magnetic field.
[0115]
[0138] Some embodiments of the present disclosure relate to a fourth method, further comprising introducing a doped additive component into the electrolytic cell, where the desired allotrope is doped and atoms of the doped additive component are incorporated directly throughout the doped desired allotrope to impart desired physical and / or chemical properties to the doped desired allotrope that differ from the undoped desired allotrope.
[0116]
[0139] Some embodiments of the present disclosure relate to a seventh CNM that includes nanorods, where the nanorods have a chunky ring-like shape.
[0117]
[0140] Some embodiments of the present disclosure relate to a seventh CNM, in which the nanorods include both carbon and oxygen.
[0118]
[0141] Some embodiments of the present disclosure relate to a seventh CNM, in which the amount of oxygen in the nanorod is between about 5% and 12% by weight.
[0119]
[0142] Some embodiments of the present disclosure provide nanorods having an I of between about 0.6 and about 0.9 as measured by Raman spectroscopy. D / I G The seventh CNM has a ratio.
[0120]
[0143] Some embodiments of the present disclosure relate to an eighth CNM comprising a nanoflower, the nanoflower comprising a number of truncated cone-shaped carbon nanotubes (CNTs) originating from a single origin, each truncated cone-shaped CNT having a diameter that decreases as the CNT extends away from the origin, the nanoflower having an I of between about 0.6 and about 0.9 as measured by Raman spectroscopy. D / I G The ratio is:
[0121]
[0144] Some embodiments of the present disclosure relate to the use of a desired nanocarbon allotrope in one or more of a medical device, a structural enhancing additive, a strength enhancing additive, an electrical conductivity enhancing additive, a thermal conductivity enhancing additive, or a flexibility enhancing additive, a hardness enhancing additive, a durability enhancing additive, a lubrication enhancing additive, or as a catalyst, an electric vehicle, a cable or wire, an athletic equipment, a pharmaceutical delivery system, an electronics, a battery, a supercapacitor, a sensor, a plastic, a polymer, a textile, a hydrogen storage system, a light absorption enhancer for a surface, an electromagnetic shielding enhancer for a surface, a surface treatment, a surface coating, a paint, or a water treatment system, wherein the desired allotrope is selected from the group of thin carbon nanotubes (CNTs), nanobamboos, nanorods, nanoonions, and nanoflowers.
[0122]
[0145] Some embodiments of the present disclosure relate to a fifth method for producing a CNM product. The fifth method includes: heating an electrolyte medium to obtain a molten electrolyte medium, positioning the molten electrolyte medium between an anode and a steel cathode of an electrolytic cell, introducing a source of carbon into the electrolytic cell, applying an electric current to the cathode and anode of the electrolytic cell, and collecting the CNM product from the cathode. In these embodiments of the fifth method, the CNM product includes a minimum relative amount of metal-coated CNM product.
[0123]
[0146] Some embodiments of the present disclosure relate to a fifth method, further comprising the step of introducing an excess amount of metal into the molten electrolyte medium.
[0124]
[0147] Some embodiments of the present disclosure relate to a fifth method, in which the excess amount of metal is introduced by introducing a metal-containing additive, by introducing the excess amount of metal by disintegrating the inner wall of the electrolytic cell, by introducing the excess amount of metal by disintegrating the anode, or by any combination thereof.
[0125]
[0148] Some embodiments of the present disclosure relate to a fifth method, wherein the metal is nickel, iron, titanium, tin, copper, vanadium, cobalt, zinc, magnesium, aluminum, ruthenium, silver, iridium, palladium, rhodium, or platinum.
[0126]
[0149] Some embodiments of the present disclosure relate to a fifth method, in which the metal is introduced as a metal mixture, a metal oxide, a metal salt, or any combination thereof.
[0127]
[0150] Some embodiments of the present disclosure are suitable for use with a current of about 0.1 A / cm 2 ~about 0.3A / cm 2 A fifth method relates to a current density between
[0128]
[0151] Some embodiments of the present disclosure relate to a fifth method, wherein the steel cathode comprises galvanized steel, stainless steel, or any combination thereof.
[0129]
[0152] Some embodiments of the present disclosure relate to a fifth method, further comprising introducing a metal additive into the electrolyte medium or the molten electrolyte medium.
[0130]
[0153] Some embodiments of the present disclosure relate to a fifth method, wherein the metal additive is added in an amount between about 0.25% and 1.5% by weight relative to the amount of electrolyte medium or molten electrolyte medium.
[0131]
[0154] Some embodiments of the present disclosure relate to a fifth method, wherein the metal additive is a nickel-containing additive.
[0132]
[0155] Some embodiments of the present disclosure are directed to a fifth method, wherein the anode comprises nickel.
[0133]
[0156] Some embodiments of the present disclosure relate to a fifth method, in which the anode has a high nickel content.
[0134]
[0157] Some embodiments of the present disclosure relate to a fifth method, further comprising adding a nickel-containing additive, wherein the anode comprises a nichrome alloy, and the minimum relative amount of metal-coated CNTs is between about 5 wt % and 99.5 wt % of the total weight of the CNM product.
[0135]
[0158] Some embodiments of the present disclosure relate to a fifth method, in which the anode is made of substantially pure nickel.
[0136]
[0159] Some embodiments of the present disclosure relate to a fifth method, in which the metal-coated CNMs are magnetic and move when in a magnetic field.
[0137]
[0160] Some embodiments of the present disclosure relate to a fifth method, further comprising introducing a doped additive component into the electrolytic cell, where the metal-coated CNM is doped and atoms of the doped additive component are incorporated directly throughout the doped, coated CNM to impart desired physical and / or chemical properties to the doped, metal-coated CNM that differ from undoped, coated CNTs.
[0138]
[0161] Some embodiments of the present disclosure relate to a ninth CNM, which includes metal-coated CNTs.
[0139]
[0162] Some embodiments of the present disclosure relate to a tenth CNM, including metal coated graphitic carbon, metal coated nanobamboo, metal coated conical carbon nanofiber, metal coated nanopearl, metal coated nanoonion, metal coated hollow nanoonion, metal coated nanoflower, metal coated nanodragon, metal coated branch and trunk CNTs (metal coated nanotrees), metal coated nanobelt, metal coated nanorod, metal coated long and / or straight CNTs, metal coated high aspect ratio CNTs, metal coated thin CNTs, and macroscopic assemblies of CNTs including closely packed, straight metal coated CNTs, metal coated nanosponge, metal coated nanoweb, or any combination thereof.
[0140]
[0163] Some embodiments of the present disclosure relate to a ninth and tenth CNM, in which the metallized CNM includes an outer coating of nickel.
[0141]
[0164] Some embodiments of the present disclosure relate to the use of a desired metal coated allotrope in one or more of a medical device, a structural enhancing additive, a strength enhancing additive, an electrical conductivity enhancing additive, a thermal conductivity enhancing additive, or a flexibility enhancing additive, a hardness enhancing additive, a durability enhancing additive, a lubrication enhancing additive, or as a catalyst, an electric vehicle, a cable or wire, an athletic equipment, a pharmaceutical delivery system, an electronics, a battery, a supercapacitor, a sensor, a plastic, a polymer, a textile, a hydrogen storage system, a light absorption enhancing agent for a surface, an electromagnetic shielding enhancing agent for a surface, a surface treatment, a surface coating, a paint, or a water treatment system, wherein the desired allotrope is metal coated CNTs, metal coated graphitic carbon, metal coated nanobamboo, metal coated conical carbon nanofibers, metal coated nanopearls, metal coated nanoonions, metal coated hollow nanoonions, metal coated nanoflowers, metal coated nanodragons, metal coated branch and trunk CNTs (metal coated nanotrees), metal coated nanobelts, metal coated nanorods, metal coated long and / or straight CNTs, metal coated high aspect ratio CNTs, metal coated thin CNTs, and macroscopic assemblies of CNTs including closely packed straight metal coated CNTs, metal coated nanosponges, metal coated nanowebs, or any combination thereof.
[0142]
[0050] Without being bound by any particular theory, embodiments of the present disclosure provide methods for making CNM products with minimum relative amounts, and in some cases high purity, of the desired nanocarbon allotropes in the CNM product. In some embodiments of the present disclosure, the methods can be scaled up to make previously unseen quantities of CNM products with minimum relative amounts or high purity of the desired nanocarbon allotropes. With such available methods, it is now possible to make large quantities of the desired allotropes, and thus various practical uses and applications of such allotropes can now be considered. In some embodiments of the present disclosure, the desired allotropes can be used in various applications, including, but not limited to, one or more of: medical devices, structural enhancing additives, strength enhancing additives, electrical conductivity enhancing additives, thermal conductivity enhancing additives, or flexibility enhancing additives, hardness enhancing additives, durability enhancing additives, lubrication enhancing additives, or as catalysts, electric vehicles, cables or wires, athletic equipment, pharmaceutical delivery systems, electronics, batteries, supercapacitors, sensors, plastics, polymers, textiles, hydrogen storage systems, or water treatment systems.
[0143]
[0051] Typically, one skilled in the art would not naturally consider modifying an established process, such as the applicant's known electrolytic process for creating carbon nanomaterials using CO2, because the complexity of such a process can be extreme without any prospect of results. Surprisingly, the presently disclosed embodiments provide for a wide range of controlled variations in electrolytic operating parameters, including variations in methods and apparatus, that successfully provide unexpected high purity of constituent structures and unusual shapes of constituent structures in the CNM product. Such controlled variations include, but are not limited to: various cathode components and compositions, composite anode components and compositions, multiple electrolyte additives, various electrolytic conditions, or combinations thereof.
[0144]
[0052] These and other features of the present disclosure will become more apparent in the following detailed description, in which reference is made to the accompanying drawings. [Brief description of the drawings]
[0145] [Figure 1] FIG. 1 is a schematic diagram showing various inputs and product outputs for the high-yield electrosynthesis of carbon nanomaterials from carbon dioxide. [Diagram 2]
[0054] Figure 3 shows scanning electron microscope (SEM) images of nanocarbon products of nanobamboo and nanopearl allotropes of carbon synthesized by electrolytic separation of CO2 in Li2CO3 at 770°C, made according to an embodiment of the present disclosure. [Diagram 3]
[0055] Transmission electron microscope (TEM) images of new nanobamboo, nanopearl, and cone-shaped CNF nanocarbon allotropes synthesized by molten carbonate electrolysis according to an embodiment of the present disclosure. [Figure 4]
[0056] Images of elemental composition analysis done by HAADF (high angle annular dark field TEM) are shown, comparing TEM of new nanobamboo and nanopearl nanocarbon allotropes synthesized by molten carbonate electrolysis according to an embodiment of the present disclosure. [Diagram 5]
[0057] A schematic diagram summarizing the growth model of carbon nanomaterials produced according to embodiments of the present disclosure is shown. [Figure 6]
[0058] TEM and HAADF elemental analysis of hollow nano-onion carbon allotropes synthesized by molten carbonate electrolysis according to an embodiment of the present disclosure. [Figure 7]
[0059] Figure 1 shows SEMs of CNM products of carbon nanoflowers, nano-onions, and nickel-coated CNT allotropes made according to embodiments of the present disclosure. [Figure 8]
[0060] Figure 1 shows SEM images of CNM products of nanodragons, nanotrees, nanobelts, and nanorod allotropes of carbon made according to embodiments of the present disclosure. [Figure 9A]
[0061] Figure 3 shows TEM and HAADF elemental analysis of nanoflower carbon allotropes synthesized by molten carbonate electrolysis according to an embodiment of the present disclosure. [Figure 9B]
[0062] Figure 6 shows TEM and HAADF elemental analysis of Nanodragon carbon allotropes synthesized by molten carbonate electrolysis according to an embodiment of the present disclosure. [Figure 10]
[0063] Figure 1 shows HAADF elemental analysis of nanotree carbon allotropes synthesized by molten carbonate electrolysis according to an embodiment of the present disclosure. [Figure 11]
[0064] A schematic diagram illustrating the observed growth of CVD-synthesized amorphous branched carbon nanotrees catalyzed by nucleating metal catalysts is shown. [Figure 12]
[0065] Figure 6 shows TEM and HAADF elemental analysis of nanobelt carbon allotropes synthesized by molten carbonate electrolysis according to an embodiment of the present disclosure. [Figure 13]
[0066] Figure 6 shows TEM and HAADF elemental analysis of nanorod carbon allotropes synthesized by molten carbonate electrolysis according to an embodiment of the present disclosure. [Figure 14]
[0067] Figure 1 shows SEM images of various allotropes of carbon synthesized by molten carbonate electrolysis according to an embodiment of the present disclosure. [Figure 15]
[0068] Figure 1 shows Raman spectroscopic analysis of CNM products consisting of various nanocarbon allotropes and filled carbon nanotube assemblies synthesized by molten carbonate electrolysis according to an embodiment of the present disclosure. [Figure 16A]
[0069] Figure 1 shows XRD analysis of CNM products consisting of various nanocarbon allotropes synthesized by molten carbonate electrolysis according to an embodiment of the present disclosure. [Figure 16B]
[0070] Figure 1 shows XRD analysis of CNM products consisting of various nanocarbon allotropes synthesized by molten carbonate electrolysis according to an embodiment of the present disclosure. [Figure 17]
[0071] Figure 1 shows an SEM image of a CNM product of high purity, high yield carbon nanotubes synthesized by molten carbonate electrolysis according to an embodiment of the present disclosure. [Figure 18]
[0072] TEM and HAADF of high purity, high yield CNTs synthesized by molten carbonate electrolysis according to an embodiment of the present disclosure. [Figure 19]
[0073] Figure 1 shows an SEM image of a CNM product of high aspect ratio (and high purity and yield) CNTs synthesized by molten carbonate electrolysis according to an embodiment of the present disclosure. [Figure 20]
[0074] TEM and HAADF analysis of a CNM product of high purity, high yield CNTs synthesized by molten carbonate electrolysis according to an embodiment of the present disclosure. [Figure 21]
[0075] Figure 1 shows an SEM image of a CNM product of high purity, high yield CNTs synthesized by molten carbonate electrolysis according to an embodiment of the present disclosure. [Figure 22]
[0076] Figure 6 shows TEM and HAADF of CNM products of carbon nanotubes exhibiting nodules or buds, synthesized by molten carbonate electrolysis, according to an embodiment of the present disclosure. [Diagram 23]
[0077] Figure 1 shows an SEM image of a CNM product consisting of carbon nanotubes arranged in macroscopic assemblies synthesized by molten carbonate electrolysis according to an embodiment of the present disclosure. [Figure 24]
[0078] Raman spectroscopy analysis of CNM products consisting of various macroscopic assemblies of CNTs synthesized by molten carbonate electrolysis according to an embodiment of the present disclosure. [Diagram 25]
[0079] Figure 1 shows XRD analysis of CNM products consisting of various CNT macroscopic assemblies synthesized by molten carbonate electrolysis according to an embodiment of the present disclosure. [Figure 26]
[0080] FIG. 1 is a line graph of mass (%) versus temperature (° C.) for high purity carbon nanotube allotropes produced according to embodiments of the present disclosure. [Figure 27]
[0081] A series of various magnified SEM images of high purity carbon nanotube allotropes produced according to embodiments of the present disclosure. [Figure 28]
[0082] A line graph of mass (%) and temperature (°C) of high purity carbon nano-onion allotrope produced according to an embodiment of the present disclosure. [Figure 29]
[0083] A series of various magnified SEM images of high purity carbon nano-onion allotropes produced according to embodiments of the present disclosure. [Diagram 30]
[0084] A line graph of mass (%) and temperature (°C) for high purity carbon nanopearl allotropes produced according to embodiments of the present disclosure. [Diagram 31]
[0085] A series of various magnified SEM images of high purity carbon nanopearl allotropes produced according to embodiments of the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0146]
[0086] The embodiments of the present disclosure relate to methods and apparatus for producing carbon nanomaterial (CNM) products containing various desired carbon allotropes, such as: carbon nanotubes (CNTs), graphitic carbon, nanobamboo, conical carbon nanofibers, nanopearl carbon, coated CNTs, nanoonions, hollow nanoonions, nanoflowers, nanodragons, branch and trunk CNTs (nantrees), nanobelts, nanorods, long and / or straight CNTs, high aspect ratio CNTs, thin CNTs, and macroscopic assemblies of CNTs. The methods and apparatus use carbon dioxide (CO2) as a reactant in an electrolytic reaction to produce these various components of the CNM products. The embodiments of the present disclosure provide a range of controlled variations of the electrolytic methods and apparatus of the present disclosure to selectively provide CNM products having high purity of one or more of these allotropes. Figure 1 provides a chart showing various CNM products that can be produced by electrolytic synthesis using carbon dioxide. In summary, FIG. 1 illustrates how CO2 can operate as a source of captured carbon 102, where CO2 is captured from the atmosphere 108 or from a more concentrated source, such as a flue gas or other industrial waste stream 110 that is a concentrated source of CO2. As will be appreciated by those skilled in the art, any source of carbon contained in a solid, gas, or liquid phase is contemplated herein. Carbon, such as CO2, is then introduced into an electrolysis cell, and an electrolysis reaction 104 occurs in a molten carbonate electrolyte medium. Products of the electrolysis reaction 104 can include oxygen and CNM products 106. Depending on the particular operating parameters of the electrolysis reaction 104, the CNM products 106 can include the desired relative amounts of the desired allotropes.
[0147] Some embodiments of the present disclosure relate to methods and apparatus for producing a CNM product containing desired carbon allotropes with a higher relative amount of a particular desired carbon allotrope. For example, the higher relative amount of the first desired carbon allotrope may be at least 20% by weight (relative to the weight of the first desired carbon allotrope compared to the total weight of the CNM product). In some embodiments of the present disclosure, the higher relative amount of the first desired carbon allotrope may be at least 25% by weight, at least 30% by weight, at least 35% by weight, at least 40% by weight, at least 50% by weight, at least 60% by weight, at least 70% by weight, at least 80% by weight, at least 90% by weight, at least 91% by weight, at least 92% by weight, at least 93% by weight, at least 94% by weight, at least 95% by weight, at least 96% by weight, at least 97% by weight, at least 98% by weight, at least 99% by weight, or at least 99.5% by weight of the total weight of the CNM product produced according to embodiments described herein. Some embodiments of the present disclosure produce CNM products with high purity of the desired allotrope.
[0148]
[0088] Definition
[0149]
[0089] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this disclosure belongs.
[0150]
[0090] As used herein, the term "about" refers to an approximate ±10% variation from a given value. It is to be understood that such a variation is always included in any given value provided herein, whether or not specifically stated.
[0151]
[0091] As used herein, the term "allotrope" may be used synonymously with "physical form," "structure," "morphology," "nanocarbon allotrope," "nanocarbon physical form," "nanocarbon structure," or "nanocarbon morphology," all of which terms - and similar terms - refer to the three-dimensional shape - and associated physicochemical properties - of the nanoscale structures found as components in CNM products produced by the embodiments described herein.
[0152]
[0092] As used herein, the terms "desired relative amount," "relative amount," or "minimum relative amount" refer to the relative amount that the desired allotrope contributes to the total amount of CNM product, which in some embodiments is greater than at least 70% by weight of the total amount of CNM product made, and the term "high purity" may also be used herein. In some embodiments of the present disclosure, the relative amount of the desired allotrope is greater than 75% by weight of the total amount of CNM product made, greater than 80% by weight of the total amount of CNM product made, greater than 85% by weight of the total amount of CNM product made, greater than 90% by weight of the total amount of CNM product made, greater than 95% by weight of the total amount of CNM product made, greater than 97.5% by weight of the total amount of CNM product made, or greater than 99% by weight of the total amount of CNM product made.
[0153]
[0093] Embodiments of the present disclosure will now be described, which include examples and references to figures.
[0154] Some embodiments of the present disclosure relate to a method for producing a CNM product containing a greater amount of a desired allotrope relative to other allotropes present in the CNM product, the method includes heating a carbonate electrolyte to obtain a molten carbonate electrolyte, positioning the molten carbonate electrolyte between an anode and a cathode in an electrolysis cell, applying an electric current to the cathode and the anode in the electrolysis cell, and collecting the CNM product from the cathode.
[0155]
[0095] In some embodiments of the present disclosure, the method further comprises selecting an anode or cathode material to synthesize a greater amount of the desired allotrope relative to other allotropes present in the CNM product. In some embodiments of the present disclosure, the method further comprises selecting an additive and adding a selected amount of the selected additive to the electrolyte to synthesize the desired nanocarbon allotrope. In some embodiments of the present disclosure, the method comprises applying a current of a selected current density to synthesize the desired nanocarbon allotrope. In some embodiments of the present disclosure, the method comprises applying a current for a selected period of time to synthesize the desired nanocarbon allotrope.
[0156]
[0096] Heating the carbonated electrolyte can be accomplished by various means, as can be understood by the skilled reader. For example, a heating device such as an oven or furnace can be used to heat the electrolyte to a sufficient temperature so that it transitions to a molten liquid state. Thus, any heating device capable of achieving the temperature required to heat the electrolyte to its melting point is contemplated herein. In some embodiments of the present disclosure, the method further includes aging the molten electrolyte, whereby the molten electrolyte is held in a molten state at a substantially constant temperature to allow a steady state to be achieved. For example, the molten electrolyte can be aged for between 1 hour and 48 hours.
[0157] The molten electrolyte is then placed between the anode and cathode of the electrolytic cell, which may also be referred to as the case. The electrolytic cell may be any type of cell capable of maintaining its structural integrity in the face of the electrochemical environment occurring during the electrolytic reaction of the present disclosure. The electrolytic cell may have one or more walls that may be made of a desired material or may be coated with a desired material that does not decompose in the environment of the electrolytic reaction. Table 1 below provides a detailed list of various electrode materials suitable for use in the embodiments of the present disclosure. In some embodiments of the present disclosure, the electrolytic cell is made of substantially pure alumina. In other embodiments of the present disclosure, the electrolytic cell is made of stainless steel with or without a lining composed of another metal, such as Inconel, Nichrome, or Monel, or a combination thereof. In some embodiments of the present disclosure, the electrolytic cell is a tubular cell with a closed end. In other embodiments of the present disclosure, the electrolytic cell is a rectangular cell with one or more compartments.
[0158]
[0098] In some embodiments of the present disclosure, the electrolyte may be melted in the electrolysis cell or melted outside the cell and transferred thereto. Since the electrolysis reaction will typically occur over a period of time, which may cause the molten electrolyte to cool, the electrolysis cell may be configured with its own integral heating device, or may be self-heated by the CO2 dissolution reaction and the electrolysis reaction, or may be configured to be heated by an external heating device outside the electrolysis cell, such that the electrolyte is maintained in a molten state for a desired period of time.
[0159]
[0099] In some embodiments of the present disclosure, the electrolysis cell may be configured to maintain an electrolysis temperature of at least about 400°C, at least about 500°C, at least about 550°C, at least about 600°C, at least about 650°C, at least about 675°C, at least about 700°C, at least about 725°C, at least about 750°C, at least about 775°C, at least about 800°C, at least about 825°C, at least about 850°C, at least about 875°C, at least about 900°C, at least about 1000°C, or greater than 1000°C.
[0160]
[0100] The anode can be made of various metals or alloys. Some anodes can be made of materials that contain metals that are resistant to corrosion by oxidation (or otherwise precious metals, such as: iridium, platinum, gold, ruthenium, rhodium, osmium, palladium, or any combination thereof). The anode can also be made of non-precious metals or mixtures of metals that are substantially pure metals, such as nickel. Some non-limiting examples of metals suitable for the anode of the present disclosure include: substantially pure nickel, alloys that are substantially mostly composed of nickel, alloys with high nickel content, or alloys that are composed of some nickel. As used herein, alloys with more than 50% by weight of nickel are referred to as high nickel content alloys. Suitable examples of alloys for use as anodes include, but are not limited to: Inconel 718 (nickel content of at least about 72% by weight), Inconel 600 (nickel content of about 52.5% by weight), or other Inconels, such as, but not limited to, Inconel 625 (nickel content of about 58% by weight), Nichrome A (composed of about 80% by weight nickel and about 20% by weight chromium), Nichrome C (composed of about 60% by weight nickel, about 24% by weight iron, and about 16% by weight chromium). Anodes made from lower nickel content alloys may be suitable for use in some embodiments of the present disclosure, including Incoloy alloy - Incoloy 800, composed of about 40% by weight iron, about 30-35% by weight nickel, and about 19-23% by weight chromium). In some embodiments of the present disclosure, the anode may be monolithic or may be a composite composed of various materials.
[0161]
[0101] In some embodiments, the anode may be planar in shape and can be made in a variety of dimensions. In some embodiments of the present disclosure, the anode may be made of a wire wound into a substantially flat coil with an upper surface and a lower surface. In some embodiments of the present disclosure, the anode may be perforated. In other embodiments, the anode may be configured with various shapes and surface modifications to maximize the active area of the electrolysis. The upper and lower surfaces of the anode may have substantially equal areas suitable for fitting into an electrolysis cell. In some embodiments, the anode surface is approximately 1 cm 2 ~Approx. 100,000cm 2 Between: approx. 10cm 2 ~50,000cm 2 or about 100cm 2 ~Approx. 10,000cm 2 In some embodiments of the present disclosure, the anode may have two or more anode faces, each within these ranges. In some embodiments, the anode may be even larger with a larger surface area. One of ordinary skill in the art will appreciate that the size of the electrolytic cell may determine the size of the anode, and vice versa. The anode may be configured to be generally aligned in a horizontal or vertical plane, or in a plane that is not parallel to either the horizontal or vertical plane.
[0162]
[0102] The cathode can be made of various metals or alloys. Some cathodes can be made of materials including steel, galvanized steel, stainless steel, copper, or any combination thereof. Some additional non-limiting examples of materials suitable for the anode of the present disclosure include: nickel, Nichrome C, Monel (about 67% nickel and about 31-33% copper by weight), and Muntz brass (about 60% copper and about 40% zinc by weight).
[0163] In one embodiment, the cathode may be planar in shape and can be made in a variety of dimensions. In some embodiments of the present disclosure, the cathode may be made of wire wound into a flat coil with an upper surface and a lower surface. In other embodiments, the cathode may be configured with a variety of shapes and surface modifications to maximize the active area for electrolysis. The upper and lower surfaces of the coiled cathode may have substantially equal areas suitable for fitting into an electrolysis cell. In some embodiments, the coiled cathode surface may be approximately 1 cm2. 2 ~about 5000cm 2 Between: about 2cm 2 ~3000cm 2 or about 3 cm 2 ~About 1000cm 2 In some embodiments, the cathode may be even larger with a larger surface area. One of ordinary skill in the art will appreciate that the size of the electrolysis cell and / or the size of the anode may determine the size of the cathode, for example, and the electrodes may be of substantially similar size. The cathode may be configured to be generally aligned with a horizontal or vertical plane, or with a plane that is not parallel to either the horizontal or vertical plane.
[0164]
[0104] In some embodiments of the present disclosure, the size and orientation of the cathode can be selected to substantially reflect the size and orientation of the anode.In some embodiments of the present disclosure, the anode and the cathode can be generally aligned with respect to a horizontal plane and spaced apart vertically from each other.In other embodiments of the present disclosure, the anode and the cathode can be generally aligned with respect to a vertical plane and spaced apart horizontally from each other.As will be understood by those skilled in the art, the distance between the electrodes must allow sufficient current to pass between them, but the amperage of the current and the size of the electrolysis cell can affect how far apart the electrodes are spaced apart. In some embodiments of the present disclosure, the electrodes may be spaced apart from each other by about 0.25 cm, about 0.5 cm, about 0.75 cm, about 1 cm, about 1.25 cm, about 1.5 cm, about 1.75 cm, about 2 cm, about 3 cm, about 4 cm, about 5 cm, about 7.5 cm, about 10 cm, about 15 cm, about 20 cm, about 30 cm, or more.
[0165]
[0105] Some embodiments of the present disclosure relate to larger, scaled-up electrolysis cells and sets of electrodes. For example, in some embodiments of the present disclosure, the electrodes are each about 1 m 2 ~about 10m 2 Between the two, about 2m 2 ~ approx. 9m 2 Between the two, about 3m 2 ~ approx. 8m 2 Between the two, about 4m 2 ~about 7m 2 Between the two, about 5m 2 ~about 6m 2 As will be appreciated by one of ordinary skill in the art, the dimensions of the electrodes may or may not match one another, or may be configured in a sandwich configuration, with one electrode located between two of the other electrodes, or in other configurations, and the dimensions of the electrodes may determine the dimensions of the electrolytic cell in which they are used.
[0166]
[0106] To initiate and maintain the electrolysis reaction in the electrolysis cell, a current is applied and passed between the anode and the cathode through the molten electrolyte therebetween. In some embodiments of the present disclosure, the current may be alternating or direct. In some embodiments of the present disclosure, the current may be between about 0.01 amperes (A) and about 5 A. In some embodiments of the present disclosure, the current may be between about 0.025 A and about 4 A; between about 0.05 A and about 3 A; between about 0.075 A and about 2 A; between about 0.1 A and about 1 A. In some embodiments of the present disclosure, the current is about 0.5 A. In some embodiments of the present disclosure, the current may be between about 5 A and about 500,000 A; or between about 500 A and 50,000 A. In other embodiments of the present disclosure, the current may be between about 5,000 A and about 50,000 A.
[0167] In some embodiments of the present disclosure, the current is applied at a substantially constant current density. For example, the current density of the applied current is about 0.001 A / cm 2 ~About 1A / cm 2 In some embodiments, the current density of the applied current may be between about 0.0025 A / cm 2 ~about 0.75A / cm 2 Between 0.005A / cm 2 ~about 0.5A / cm 2 Between 0.0075A / cm 2 ~about 0.25A / cm 2 or about 0.01A / cm 2 ~about 0.1A / cm 2 In other embodiments of the present disclosure, the current density of the applied current may be between about 1 A / cm 2 ~about 10A / cm 2 In some embodiments, a low current density is used to control the conductivity during the formation of the CNM product.
[0168] In some embodiments of the present disclosure, the method further includes ramping up the current in incremental increments over a predefined time period. For example, a first period of a first constant current density is followed by a second period of a second constant current density, then a third period of a third constant current density, then a fourth period of a fourth constant current density, and so on until a final current density is applied for the duration of the electrolysis process. In these examples, the periods may be the same or different and may range from 1 minute to 1 hour, or any time in between. In these examples, the constant current density may be the same or different and may range from 0.005 A / cm 2 ~0.75A / cm 2 In other embodiments, the ramp current may increase and / or decrease in a stepwise manner, such as by oscillation or by a linear ramp change or by other variations.
[0169]
[0109] In some embodiments of the present disclosure, the method further includes a step of introducing an additive or additives, which may also be referred to herein as adding, into the carbonate electrolyte medium. This step of introducing can be achieved by various techniques, depending on the nature of the additive. The step of introducing the additive into the carbonate electrolyte can be performed before, during, or after the carbonate electrolyte is heated to a molten state. Non-limiting examples of such additives include: lithium-containing additives (such as lithium phosphate; lithium oxide, and other lithium-containing salts); iron-containing additives (such as iron-containing salts including iron oxide); magnesium-containing additives (such as magnesium salts including magnesium oxide); transition metal nucleating agents (such as Fe2O3, nickel powder, chromium powder); one or more transition metal salts of iron, nickel, chromium, nickel, copper, manganese, titanium, zirconium, molybdenum, tantalum, or cobalt. For clarity, additives that do not contain any iron (including iron-containing salts) are collectively referred to herein as "iron-free" additives. In non-limiting embodiments of the present disclosure, the iron-free additive includes: an additive that is substantially free of any iron, an additive that contains trace amounts of iron, and / or an additive that contains an amount of iron that does not participate in the electrolytic reaction in any substantial or significant manner. Examples of iron-free additives include, but are not limited to: a lithium-containing additive, a cobalt-containing additive, a nickel-containing additive, and a chromium-containing additive. According to embodiments of the present disclosure, the additive may be introduced in an amount between about 0.01% and 10% by weight based on the amount of the electrolyte medium or molten electrolyte medium. In some embodiments of the present disclosure, the additive may be introduced in an amount between about 0.05% and about 7.5% by weight based on the amount of the electrolyte medium or molten electrolyte medium. In some embodiments of the present disclosure, the additive may be introduced in an amount between about 0.075% and about 5% by weight based on the amount of the electrolyte medium or molten electrolyte medium.
[0170]
[0110] As a further example, in some embodiments of the present disclosure, the lithium-containing additive may be added in an amount between 0.01 wt % and about 10 wt %, or between about 0.05 wt % and about 9 wt %, or between about 0.075 wt % and about 8 wt %.
[0171]
[0111] By way of further example, in some embodiments of the present disclosure, the iron-containing additive may be added in an amount between 0.01 wt. % and about 5 wt. %, or between about 0.05 wt. % and about 2.5 wt. %, or between about 0.075 wt. % and about 1.25 wt. %, and in further embodiments, the iron-containing additive is added in an amount between about 0.05 wt. % and 0.15 wt. %.
[0172]
[0112] By way of further example, in some embodiments of the present disclosure, the nickel-containing additive (either as nickel powder or a nickel salt) may be added in an amount of between 0.01 wt. % and about 5 wt. %, or between about 0.05 wt. % and about 2.5 wt. %, or between about 0.075 wt. % and about 1.25 wt. %, and in further embodiments, the nickel-containing additive is added in an amount of between about 0.05 wt. % and 0.15 wt. %.
[0173]
[0113] By way of further example, in some embodiments of the present disclosure, the cobalt-containing additive (either as cobalt powder or a cobalt salt) may be added in an amount of between 0.01 wt % and about 5 wt %, or between about 0.05 wt % and about 2.5 wt %, or between about 0.075 wt % and about 1.25 wt %, and in further embodiments, the cobalt-containing additive is added in an amount of between about 0.05 wt % and about 0.15 wt %.
[0174]
[0114] By way of further example, in some embodiments of the present disclosure, the chromium-containing additive (either as chromium powder or a chromium salt) may be added in an amount between 0.01 wt. % and about 5 wt. %, or between about 0.05 wt. % and about 2.5 wt. %, or between about 0.075 wt. % and about 1.25 wt. %, and in further embodiments, the chromium-containing additive is added in an amount between about 0.05 wt. % and about 0.15 wt. %.
[0175] In some embodiments, the transition metal nucleating agent may be a transition metal oxide. In some embodiments of the present disclosure, the nucleating agent may be incorporated into the CNM product, such that the atoms of the nucleating agent form part of one or more allotropes of the CNM product. In some embodiments of the present disclosure, the incorporated nucleating agent may be magnetic. In some embodiments of the present disclosure, a portion of the nanomaterial product may be responsive to a magnetic field (by moving when near or in a magnetic field) and a portion may be unresponsive to a magnetic field (by not moving), and these two types of nanomaterial products may be separated by applying an external magnetic field.
[0176]
[0116] The total duration of the electrosynthesis process may be between about 10 minutes and about 156 hours.
[0177]
[0117] In some embodiments of the present disclosure, the selecting step may be configured so that the CNM product contains a desired combination of two or more desired allotropes. For example, the selecting step may be varied in a controlled manner so that the CNM product contains a first allotrope and a second allotrope or additional allotropes. Furthermore, the selecting step may be configured to achieve a desired relative amount of the first allotrope and the second allotrope relative to each other in the CNM product. For example, it may be desired that the amount of the first allotrope is greater than, less than, or substantially equal to the amount of the second allotrope present in the CNM product.
[0178]
[0118] As will be understood by those skilled in the art, the particular variations in the electrolytic process conditions, also referred to herein as operating parameters, described herein may vary even more as the physical scale of the electrolytic process increases. EXAMPLES
[0179]
[0119] Example
[0180]
[0120] The components of the molten electrolyte mixture described herein are commercially available: lithium carbonate (Li2CO3; Alfa Aesar, approximately 99% pure), lithium oxide (Li2O, 99.5%, Alfa Aesar), lithium phosphate (Li3PO4, 99.5%), iron oxide (Fe2O3, 99.9%, Alfa Aesar), and boric acid (H3BO3, Alfa Aesar 99+%).
[0181]
[0121] In the electrodes described herein: Nichrome A (0.04 inch thick), Nichrome C (0.04 inch thick), Inconel 718, Inconel 600 (0.25 inch thick), Inconel 625 (0.25 inch thick), Monel 400, Stainless Steel 304 (0.25 inch thick), Muntz Brass (0.25 inch thick), Nickel, Iridium were all purchased from conventional commercial metal suppliers. Composite electrodes were fabricated from these purchased materials or purchased as used.
[0182] For the additives described herein: Ni powder is 3-7 μm (99.9%, Alfa Aesar), Cr powder is <10 μm (99.2%, Alfa Aesar), Co powder is 1.6 μm (99.8%, Alfa Aesar), and iron oxide is 99.9% Fe2O3 (Alfa Aesar). Inconel 600 (100 mesh) was purchased from Cleveland Cloth. Electrolysis was performed in a high form crucible >99.6% alumina (Advalue).
[0183]
[0123] The specific electrolyte composition of each electrolyte is described herein. The electrolyte was premixed in the weight ratio described, and then metal or metal oxide additives, if used, were added. The cathode was mounted vertically opposite the anode and immersed in the electrolyte. Generally, the electrodes were immersed following dissolution of the electrolyte. For example, for some electrolytes, once dissolved, the electrolyte was maintained at 770°C ("aging" the electrolyte), and then the electrolyte was immersed and then electrolyzed immediately. Generally, the electrolysis was carried out at a constant current density as described. As described, for some electrolytes, the current density was increased in several steps to the applied electrolysis current and then maintained at a constant current density. Otherwise, the electrolysis was started and held at a single constant current. The electrolysis temperature was about 770°C unless otherwise indicated herein.
[0184]
[0124] Sources of carbon included CO2 captured directly from air and CO2 from the flue gas of a natural gas power plant. In embodiments of the present disclosure, electrolytic separation can occur as direct air carbon capture, with or without CO2 preconcentration, with concentrated CO2, or with a gas containing CO2, such as flue gas.
[0185] CNM products made according to the following examples were washed (deionized water, 6M HCl, concentrated HCl) to remove excess electrolyte, separated from the wash solutions, and analyzed by PHENOM Pro Pro-X scanning electron microscope (SEM, by EDX), FEI Teneo LV SEM, and FEI Teneo Talos F200X TEM (by EDX). XRD powder diffraction analysis was performed on a Rigaku D=Max 2200 XRD diffractometer and analyzed with the Jade software package. Raman spectroscopy was performed using 532.14 wavelength incident laser light, high resolution 0.6 cm -1 The measurements were performed using a LabRAM HR800 Raman microscope (HORIBA).
[0186]
[0126] In some embodiments of the present disclosure, the CNM product made by the methods, apparatus, and systems described hereinbefore may provide high purity of desired allotropes, doped with such desired allotropes. Without being bound to any particular theory, when a doping component, also referred to as a dopant, is introduced into the method, apparatus, or system, the atoms of the dopant may be directly incorporated into the various graphitic structures of the CNM product and into the desired allotropes therein. When the atoms of the doping component are directly incorporated into the CNM product, as constructed in situ on the cathode, the resulting doped CNM product has desired chemical and physical properties that differ from a CNM product that does not contain the atoms of the doping component (an undoped CNM product). Without being bound to any particular theory, the doping component may include at least one material including a Group IIIA element, a non-carbon Group IVA element, a Group VA element, a Group VIA chalcogenide element, or at least one material including gold, platinum, iridium, iron, or other period 4, 5, or 6 metals. In some embodiments of the present disclosure, the doping component includes one or more of: chemical species with oxygen atoms, halide atoms, nitrates, phosphates, thiophosphates, silicates, thionyl chloride, sulfur chloride, silicon chloride, thiophosphates, thionyl nitrate, silicon nitrate, silicon nitrite, sulfur oxide, and nitrous oxide gas. Without being bound to any particular theory, the desired chemical properties of the doped CNM product may include: greater electrical conductivity (compared to undoped CNM products), enhanced charge storage (compared to undoped CNM products), heterogeneous catalytic properties, homogeneous catalytic properties, fuel cell catalytic properties, aerobic oxidation catalytic properties, enhanced reaction activity properties, and any combination thereof. The desired physicochemical properties of the doped CNM products made according to embodiments of the present disclosure may have a wide variety of applications, such as: catalysis, heavy metal removal, energy storage, sorption applications, batteries, ultrasensitive sensors, and combinations thereof.
[0187]
[0127] In some embodiments of the present disclosure, the CNM product produced by the methods, apparatus, and systems described hereinbefore can result in the desired allotrope being magnetic. For clarity, the magnetic CNM product and the magnetic allotrope therein can be physically moved by a magnetic field. Without being bound to any particular theory, when the magnetic additive component is introduced into the method, apparatus, or system, carbide-driven growth of various graphite structures in the magnetic CNM product can occur. In some embodiments of the present disclosure, the magnetic additive component includes at least one of a magnetic material additive component, a carbide growth component, and any combination thereof. In some embodiments of the present disclosure, the magnetic material additive component includes one or more magnetic materials having ferromagnetic, paramagnetic, diamagnetic, and any combination thereof, including iron, nickel, cobalt, gadolinium, samarium, neodymium, steel, and alloys. In some embodiments of the present disclosure, the iron-based additive is one or more of cast iron powder, iron metal, steel, stainless steel, iron-containing metal alloy, iron oxide, FeO, Fe2O3, Fe3O4, or iron-containing salt. In the magnetic CNM product, the magnetic additive component may be incorporated or formed as one or more nodules, which may be covered on the magnetic CNM product with one or more layers of graphitic carbon. In some embodiments of the present disclosure, the carbide growth component may be a metal carbide, such as iron carbide, nickel carbide, cobalt carbide; zirconium carbide, chromium carbide, tantalum carbide, hafnium carbide, and any combination thereof. In some embodiments of the present disclosure, the carbide growth component may be a non-metal carbide, such as silicon carbide, germanium carbide, and any combination thereof. The magnetic additive component may be added to the methods, apparatus, and systems of the present disclosure as a chemical additive, or may originate from one or more walls of the electrolytic cell, the anode, the cathode, the electrolyte medium, and any combination thereof.
[0188] Example 1 Electrolytic process conditions for producing nanocarbon products with desired allotropes of high purity
[0189] To produce the CNM product, the electrolysis reaction was carried out in an electrolyte cell that included a tank, an anode, and a cathode. The tank was made of pure alumina (99.6% pure alumina, commercially available from AdValue) and had a closed end. The tank contained molten Li2CO3 electrolyte at 770°C.
[0190]
[0130] The anodes were made from a variety of materials and configured to generate oxygen during the electrolysis reaction.
[0191]
[0131] The cathode was also constructed from brass and into a substantially flat coil.
[0192]
[0132] Carbon dioxide from the air was captured directly by the molten electrolyte during the electrolysis reaction.
[0193]
[0133] The various electrochemical operating parameters were the composition and / or configuration of the cathode and anode, the additives and their concentrations used in the Li2CO3 electrolyte, the current density, and the time of electrolysis. The various electrolyte additives included Fe2O3, nickel, chromium powder, or combinations thereof. The electrolysis reactions were varied over a range of electrolysis current densities. The electrode variations included the use of cathodic metal electrodes such as Muntz brass Monel, or Nichrome alloys. The anode types included precious metal anodes, such as iridium, various nickel-containing anodes including nickel, Nichrome A or C, Inconel 600, 625, or 718, or specific layered combinations of these metals. The alloy compositions of the metals used as electrodes are presented in Table 1. Metallic variations were further refined by combining the metals in Table 1 as the anode using a solid sheet of one Inconel alloy layered with one or more screens of another Inconel alloy, e.g., an anode of Inconel 625 with three layers (spot welded) of 100 mesh Inconel 600 screen.
[0194]
[0134] [Table 1]
[0195]
[0135] Thousands of runs of various combinations of electrolysis operating conditions were conducted to realize the embodiments of the present disclosure. Fewer than 30 of these electrolysis produced attractive but rarely observed products that had nanomorphological analogues to the bamboo macrostructure, but were only observed in a low percentage of the total products. Table 2 summarizes the systematic optimization of electrolysis conditions in Li2CO3 at 770°C to optimize and maximize electrolyte formation of nanobamboo. Several conventional electrolysis to produce nanobamboo have been associated with nickel electrodes or initiated by ramping the current to stimulate nucleation. Experimental electrolysis #I in the top row of Table 2 includes both of these features, including nickel as both the cathode and anode. Ramp-up increments of electrolysis current were also applied as follows: constant 0.01, then 0.02 A / cm 2 Then, for another 10 minutes, the initial 10 minutes of electrolysis was followed by 0.04, then 0.08 A / cm 2 Electrolysis was continued for another 5 min at 0.2 A / cm2, followed by constant current electrolysis at 0.2 A / cm2. 2 As shown in Table 2, electrolysis #II was performed with 100% NaOH. Nanobamboo was evident in the product SEM but constituted a small amount (30 wt%) of the total product. As seen in Table 2, electrolysis #II, an increase in nanobamboo product was realized with the direct addition of Ni and Cr additive powders to the electrolyte, and the anode was replaced by a noble metal (iridium), accompanied by a 5-fold decrease in current density. As shown in Table 2, this electrolysis #II has the first majority of nanobamboo product, 60 wt%. Coulombic efficiency quantifies the available charge measured against the number of 4 electrons measured per equivalent of C in the product (current multiplied by electrolysis time). Coulombic efficiency tends to drop with lower current density, and in this case the coulombic efficiency of the synthesis was 79%. Coulombic efficiency can approach higher values at low current densities by lowering the impurities in the system.
[0196]
[0136] [Table 2]
[0197]
[0137] Without being bound to any particular theory, the low current ramp, pre-electrolysis conditions may have benefits and drawbacks. For example, as a benefit, the current ramp conditions may favor the reduction and deposition of the initial graphene layer to facilitate ongoing reduction and growth. Additionally, the lower current may favor transition metal deposition at the cathode and formation at nucleation sites. While at low concentrations compared to carbonate (from CO2) in the electrolyte, the analysis of bound vs. free metal cations in the molten electrolyte for reduction potential calculations has been very challenging. However, without Nernst activity and temperature correction, the reduction residual potentials of Ni, Fe, Cr, and Cu and CO2 at room temperature are CO2(IV / 0) = -1.02, Cr(III / 0) = -0.74, Fe(II / 0) = -0.44, Co(II / 0) = -0.28, Ni(II / 0) = -0.25, Fe(III / 0) = -0.04, Cu(II / 0) = 0.34, and Co(III / 0) = 1.82. However, the carbonate C(IV)O3 formed by the reaction of C(IV)O2 with electrolyte oxides in pure molten carbonate solution is 2- It should be noted that the free activity of tetravalent carbon as a catalyst was orders of magnitude greater than the transition metal ion activity dissolved in the electrolytic electrolyte. This helps to drive the thermodynamic and kinetic reduction of tetravalent carbon upon metal deposition at the cathode. However, the actual observation was that for most of the molten carbonate CO2 electrolysis studied, the initial low current ramp did not appear to promote the highest purity carbon deposition.
[0198]
[0138] Figure 2 shows images of SEM analysis of nanocarbon products of nanobamboo and nanopearl allotropes of carbon synthesized by electrolytic separation of CO2 in Li2CO3 at 770 °C. Moving from left to right in the panels, the products were analyzed by SEM with increasing magnification. Scale bars in the panels (starting from the left) are: for panel III: 100, 10, 3 μm (various electrolytic), and 2 μm; for panels IV and V: 5, 2, 1, and 1 μm; for panel VII: 50, 30, 20, and 15 μm; for panel VIII: 50 μm 10, 1, and 2 μm.
[0199]
[0139] The first row of Figure 2 (panel #III) presents SEMs of the products of electrolysis #III, continuing to use a lower current density and showing a similar coulombic efficiency of 78%, focusing on the addition of Ni powder to the electrolyte and refining the anode to Inconel 718 with two layers of Inconel 600, increasing the nanobamboo product to 89 wt%. Additionally, this electrolysis used an "aged" electrolyte (not depicted in the table). Freshly melted electrolytes require time (up to 24 hours) to reach steady state equilibrium (pre-equilibration step). In electrolysis #III, the electrolyte was aged for 24 hours before melting and then immersing the electrodes. However, aging was observed to be detrimental to maximizing the nanobamboo yield. Final purification and immediate use of freshly melted electrolyte (elimination of the aging step) increases the nanobamboo product to constitute 90 wt% of the product (second row of Figure 2, and electrolysis #IV and repeated #V in Table 2). Interestingly, the 6% non-bamboo product in electrolysis #IV and V appears to be in the form of cone-shaped carbon nanofibers, CNFs, with their distinct triangular voids, as seen in the second row of Figure 2. A simplified electrolysis removes the observed CNF impurity, resulting in 95% of the nanobamboo allotrope. This electrolysis #VI uses a high current of 0.4 A / cm 2The electrolysis was performed without current ramp activation at a current density of 99.7%, showing a Coulombic efficiency of 99.7%. The electrolysis was adjusted to have an intended excess of nucleated metal, achieved both through the use of a Nichrome C electrode containing Ni, Fe, and Cr (Table 1) and through the direct addition of Ni and Cr powders to the electrolyte.
[0200]
[0140] Continued use of high concentrations of added transition metal powders in the electrolyte, and low current densities, but with changes in the electrodes, results in another quite different distinct nanocarbon allotrope, referred to herein as "hollow nano-onions". In particular, in electrolysis #VII in Table 2 and Figure 2, the same concentration of Ni powder that has been used in electrolysis #VI and V, as well as the electrolyte, was not aged and the initial current applied was not increased. However, a Monel cathode and Nichrome C anode were used, resulting in 95 wt% of the product having a distinct hollow nano-onion morphology. The hollowness of the nano-onions will be revealed by TEM, but their spheroidal character was seen by SEM in the third row of Figure 2. When the pure nickel electrolyte additive was changed to half-nickel and half-chromium powders, as summarized in Table 2 for electrolysis #VIII and IX, the product has a distinct "nano-pearl" morphology with similarity to a bead-shaped necklace. In this case, the product fraction increased to 97% of this nanopearl carbon, as shown by SEM in the bottom row of Figure 2. Electrolytes #VII-IX were performed at a low current density, J = 0.0 A / cm 2 and show a reduced coulombic efficiency of 79-80%.
[0201]
[0141] Figure 3 compares TEM images of the new nanobamboo, nanopearl, and cone-shaped carbon nanofiber (CNF) nanocarbon allotropes synthesized by molten carbonate electrolysis. As seen in the top left panel of the figure, the CNFs exhibit the cone-shaped voids typical of this CNF structure. The growth of the nanobamboo is seen in the middle left panel of the figure to be nucleation driven, with the nucleation regions appearing to change shape as they move from the tip to the interior of the structure. Without wishing to be bound by any particular theory, it is hypothesized that the lateral walls forming the bamboo "knobs" may be related to periodic deficiencies in carbon building up the preceding walls. The walls of the nanobamboo and nanopearl allotropes exhibit graphene walls characterized by a typical intergraphene wall separation of 0.33-0.34 nm, as described and measured by the separation observed in the dense carbon plane with TEM. The bottom left panel of the figure shows the lateral multiple graphene layers separating the "knobs" of the nanobamboo structure. The bottom left of the figure shows an example nanopearl allotrope defining multiple bead-like sections extending along the longitudinal axis of the nanopearl, with each bead-like section resembling an individual pearl in a string of pearls, each of which includes multiple layers of curved graphene that form the respective walls of the individual bead-like sections of the nanopearl allotrope.
[0202] FIG. 4 shows elemental composition images made by HAADF (high angle annular dark field TEM) comparing TEM of nanobamboo and nanopearl nanocarbon allotropes synthesized with molten carbonate electrolyte. As seen from the HAADF, the nanobamboo product was pure carbon, with the exception of the presence of copper, shown in the lower left corner of the top left panel, widely distributed at low concentrations throughout, which may come from the grid mount of the product sample or from the copper content when a Monel cathode is used. The HAADF probes two nanopearl samples. The first shows high or 100% concentrations of carbon (noise levels were high) and little or no Ni, Cr, or Fe. The second probes carbon with higher resolution, and rising and falling carbon levels were evident as the probe moved from left to right over two individual nanopearl structures. The top right hand panel 402 shows the elemental profile obtained along the white arrows to the left in the panel. Panels 402, 403 show HAADF data, 404 shows carbon content, 405 shows chromium content, 406 shows iron content, and 407 shows nickel content. Panel 410 on the lower right shows the elemental profile taken along the white arrow to the left in the panel. Panels 410, 403 show HAADF data, and 404 shows carbon content.
[0203]
[0143] The top row of Figure 5 shows cone-shaped variations of bamboo carbon nanofibers and their proposed growth mechanism, as formed by nickel-nucleated CVD using methane and hydrogen (Jia, K.; Kou, K.; Qin, M.; Wu, H.; Puleo, F.; Liotta, LF Controllable and Large-Scale Synthesis of Carbon Nanostructures: A review of Bamboo-Like Nanotubes. catalysts 2017, 7, 256, modified, open access). The bottom left panel of Figure 5 shows the entangled bamboo nanocarbon modification by CVD, and the top right panel of the schematic shows the proposed growth mechanism (modified from Zhang, M. He, C.; Liu, E.,; Zhiu, S., Shi, C.; Li, J.; Li, Q.; Zhao, N. Activated Carbon Nano-Chains with Tailored Micro-Meso Pore Structures and Their Application for Supercapacitors. J. Phys. Chem. C, 2015, DOI: 10.1021 / acs.jpcc.5b05480). The bottom right panel of Figure 5 shows the general graphene layer configuration occurring in carbon nanofibers (modified from Yadav, D.; Amini, F.; Ehrmann, A. Recent advances in carbon nanofibers and their applications - A review. European Polym. J. 2020, 138, 109963). In Figure 5, 502 shows the chemical vapor deposition reaction of CH3 and H2 on a nickel particle. Strong distortion is shown by 504, which indicates graphitic shell stress 506. Also shown is a particle jump 508, which results in a cone-shaped hole 510.
[0204]
[0144] Cone-shaped CNFs, nanobamboos, and nanopearls are new and unusual high-yield carbon allotropes as synthesized by molten electrolyte. Similar CVD synthesis forms have been synthesized by CVD. In particular, CVD cone-shaped CNF structures have been extensively characterized, as shown in the top row of Figure 5. The cone-shaped CNF morphology in CVD has been proposed to be due to repeated stress-induced shape deformation of the nucleating (Ni) metal, which causes the metal particles to jump and form the observed lateral graphene separations that bridge the walls of the allotrope. Spherical spaced nanobamboo and nanopearl allotropes are less common in CVD, but have been observed. An example is shown in the bottom left row of Figure 5, and the structure was attributed to the periodic formation of pores within the structure due to defects to the outer layer. One particular application of bamboo CVD CNTs is their use as a platform for building biosensors on a layer-by-layer basis. Carbon fibers are generally classified as amorphous or as constructed from graphene platelets, carbon nanotubes, or cone-type structures, as shown in the lower right side of FIG.
[0205]
[0145] Figure 6 shows TEM and HAADF elemental analysis of hollow nano-onion allotropes synthesized by molten carbonate electrolysis. Panel A shows hollow nano-onions, Panel B shows hollow nano-onions with and without trapped metal; Panel C shows hollow nano-onions with trapped metal; and Panel D shows hollow nano-onions with and without trapped metal. Panel 602 shows the elemental profile obtained along the white arrow to the left of the panel. In panel 602, 604 shows carbon content, 605 shows iron content, and 606 shows nickel content. Panel 610 shows the integral atomic fraction over D region #1 where carbon is about 98.1% and nickel is about 1.9%. Panel 620 shows the integral atomic fraction over D region #2 where carbon is essentially 100% (not counting any copper content that may be present due to the manner in which the sample was prepared for analysis).
[0206]
[0146] Figure 6 shows the elemental composition by TEM and HAADF of the new hollow nano-onion nanocarbon allotrope synthesized by molten carbonate electrolysis. The hollow nano-onion defines an inner core. As shown, some of the nano-onion inner core contains metal while others are substantially empty (void / hollow). The walls of the hollow nano-onion are composed of graphene layers as marked in the figure and characterized by a typical graphene-wall separation of 0.33-0.34 nm as measured by the separation observed between dense TEM carbon planes. As seen in the HAADF of Figure 6, when the core was hollow the nano-onion was pure carbon and when the core contained metal the metal was nickel or a combination of nickel and iron.
[0207] Example 2 Electrochemical conditions for synthesizing CNM products on nickel-coated CNTs, nano-onion allotropes, or nano-flower allotropes
[0208]
[0148] Figure 7 shows SEM of CNM products of carbon nanoflowers, nano-onions, and nickel-coated CNT allotropes by electrolytic separation of CO2 in Li2CO3 at 770 °C. Moving from left to right in the panels, the products were analyzed by SEM at increasing magnification. Scale bars (starting from the left) in panel XI: 150, 20, 15, and 2 μm; in panel XII: 50 μm; in panel XIII: 50 and 15 μm; in panel XIV: 100, 30, 15, and 10 μm; in panel XV: 100 μm, 30, and 5 μm.
[0209] Nickel anodes or excess nickel added results in nickel-coated CNTs. Rather than forming alternative allotropes such as nanobamboos or nanopearls, the use of excess nickel tends to coat the carbon nanotubes with nickel, especially when used in conjunction with: (i) a stainless steel cathode; (ii) higher electrolysis current densities when utilized; and (iii) activation with an initial current ramp. This is summarized in the top row of Table 3 as Electrolysis #X, where 0.81 wt. % Ni powder was added to the Li2CO3 electrolyte and Nichrome C was used as the anode. The electrolysis was run at 0.20 A / cm 2 The results show a coulombic efficiency of 98.9%. The Ni coating was further improved in electrolysis XI (appearing more uniform in the SEM) when a pure nickel anode was used rather than Nichrome C, but when no Ni powder was added to the electrolyte, and no current ramp was used, as shown in Table 3 and in the top row of Figure 7. The electrolysis was performed at 0.15 A / cm 2 and showed a coulombic efficiency of 93.4%.
[0210]
[0150] Without being bound by any particular theory, the presence of an excess amount of nickel among other distinct operating parameters of the electrolysis reaction is responsible for the nickel outer coating formed on the outer surface of the CNT. The excess nickel can be established in the electrolysis reaction as a result of the melting point of Li2CO3, which is 723°C, of the additive (containing a metal oxide or metal salt as the metal). Another inner wall of the electrolysis cell decomposes during the electrolysis reaction, the cathode decomposes during the electrolysis reaction, the anode decomposes during the electrolysis reaction, or any combination thereof. Thus, when the method uses other distinct operating parameters that result in nickel-coated CNTs, including a steel cathode, an excess amount of other metals or metal-containing compounds can also result in the CNTs being coated with other metals. For example, excess amounts of metals - other than nickel - including but not limited to: iron, titanium, tin, copper, vanadium, cobalt, zinc, magnesium, aluminum, ruthenium, silver, iridium, palladium, rhodium, and platinum are believed to result in metal-coated CNM products and metal-coated CNT allotropes in the CNM products. Additionally, excess amounts of metal mixtures, metal oxides, or any combination thereof are also contemplated herein. Collectively, coatings on allotropes that include one metal, metal mixtures, or metal oxides are referred to collectively as metal-coated allotropes.
[0211]
[0151] In some embodiments of the present disclosure, the entire CNM product may be coated. In some embodiments of the present disclosure, the desired allotrope in the CNM product may be coated with metal. For example, using the embodiments described herein, the method may be used to coat one or more desired allotropes with metal, including, but not limited to, metal-coated carbon nanotubes (CNTs), metal-coated graphitic carbon, metal-coated nanobamboo, metal-coated cone-shaped carbon nanofibers, metal-coated nanopearls, metal-coated nanoonions, metal-coated hollow nanoonions, metal-coated nanoflowers, metal-coated nanodragons, metal-coated branch and trunk CNTs (metal-coated nanotrees), metal-coated nanobelts, metal-coated nanorods, metal-coated long and / or straight CNTs, metal-coated high aspect ratio CNTs, metal-coated thin CNTs, and macroscopic assemblies of CNTs, including closely packed straight metal-coated CNTs, metal-coated nanosponges, and metal-coated nanowebs. In some embodiments of the present disclosure, the relative amount of metal coated allotropes - of the total amount of allotropes present in the CNM product - is between about 5% and about 99.5% by weight. In other embodiments of the present disclosure, the relative amount of metal coated allotropes is between about 7.5% and about 97.5% by weight, between about 10% and about 15% by weight, between about 20% and about 92.5% by weight, or between about 30% and about 90% by weight.
[0212]
[0152] Without wishing to be bound by any particular theory, the exclusion of transition metals from the molten electrolysis environment may hinder their activity as nucleation points for carbon growth and may inhibit the growth of carbon nanotubes. Inhibition of metal nucleation growth of CNTs, such as through the use of noble metal anodes, has been an effective means of promoting the growth of another nanocarbon: carbon nano-onions. Here, another molten electrolysis route was found to ensure high nano-onion product yields through the addition of lithium phosphate to the electrolyte. As summarized in Table 3, electrolysis XII and XIII, with the addition of 8 wt% Li3PO4 to Li2CO3 electrolyte, the product was nearly pure (97-98%) carbon nano-onions, as summarized in Table 3. This nano-onion product was obtained over a wide range of electrosynthesis current densities (0.08-0.20 A / cm 2 ), with either Muntz brass or Monel as the cathode, with (Electrolysis #XII) or without (Electrolysis #XIII) an initial current rise step during electrolysis was observed.
[0213]
[0153] Various low current densities, Muntz brass cathode, Nichrome C anode, and aged electrolytes lead to an attractive new high purity molten electrolytic nanocarbon allotrope: nanoflowers. In particular, after aging the electrolyte for 24 hours, excess (0.081 wt%) chromium metal powder was added to the electrolyte. The electrolysis was performed at 0.08 A / cm. 2The electrolysis was performed at 1000 nm and showed a coulombic efficiency of 78%. The electrolysis was repeated (as electrolysis #XIV and XV) and gave the same results summarized in Table 3 and shown by SEM in Figure 7. As seen in the bottom right panel of Figure 7, the products appear as hollow tubes within a flower morphology. Enlargement of these hollow tubes by TEM HAADF (not shown) confirms that they occur both individually and as interconnected aggregates. However, the product morphology is highly unusual in some aspects. Multiple CNTs emerge from the origin of origin giving a flower-like arrangement. Without wishing to be bound by any particular theory, this may represent base growth rather than tip growth and multiple growth patterns activated from a single activation point. An alternative mechanism to be explored is tip growth, where the metal nucleated tips sinter (reducing size) as growth proceeds, with continued growth reducing the diameter of the nanocarbon products. The CNTs appear as short, very straight spikes. The CNTs are truncated cones with a decreasing diameter as they extend away from the origin. Small percentages of platelets and garnet-like material were scattered throughout the floral configuration. Although new as the majority of molten electrolytic CNM products, nanoflowers have been observed and described not only from carbon, but also from gold, platinum, and silver, as well as from zinc and titanium oxides.
[0214]
[0154] [Table 3]
[0215] Example 3 Electrochemical operating parameters for the synthesis of CNM products with desired allotropes of nanodragons, nanotrees, nanobelts, and nanorods
[0216]
[0156] Figure 8 shows SEM images of CNM products of nanodragon, nanotree, nanobelt, and nanorod allotropes of carbon by electrolytic separation of CO2 with Li2CO3 at 770 °C. Moving from left to right in the panels, the products were analyzed by SEM with increasing magnification. Starting from the left, scale bars in panel K: 50, 10, 5, and 5 μm; in panel Q: 100, 100, 5, 1, and 100 μm; in panel Y: 50, 5, and 5 μm; in panel Z: 30, 10, 5, and 1 μm.
[0217]
[0157] Figure 9A shows TEM and HAADF elemental analysis of nanoflower allotrope synthesized by molten carbonate electrolysis according to an embodiment of the present disclosure. Panel 904 shows the elemental intensity profile taken along the white arrow. Panel 906 shows the elemental intensity profile taken along the white arrow to the left in the panel. Figure 9B shows TEM and HAADF elemental analysis of nanodragon carbon allotrope 902 synthesized by molten carbonate electrolysis according to an embodiment of the present disclosure. Panel 910 shows the integrated atomic fraction over E region #1 where carbon is substantially 100% (without considering any copper content).
[0218]
[0158] Figure 10 shows the HAADF elemental analysis of nanotree carbon allotropes synthesized by molten carbonate electrolysis. Panel 1010 shows the elemental intensity profile taken along the white line to the left in panel I below, where 1011 indicates the carbon content, 1012 indicates the iron content, and 1013 indicates the nickel content.
[0219]
[0159] Figure 11 shows a schematic diagram showing the observed growth of CVD-synthesized amorphous branched carbon nanotrees catalyzed by iron carbide (included as yellow domains). In the left panel, a-f and g-k show the fraction of yellow iron carbide nucleation sites resulting in one or more purple carbon branches (Modified from Takai, A.; Ataee-Esfahani, H.; Doi, Y.; FuiqE, M.; Yamauchi, Y.; Kuroda, K. Pt nanoworms: creation of a bumpy surface on one-dimensional (1D) Pt nanowires with the assistance of surfactants embedded in mesochannels. Chem. Comm. 2011, 47, 7701-7703). The right panel shows a schematic diagram showing the structure of CVD-synthesized carbon nanobelts (modified from He, Z.; Maurice, J.-L. Lee, C.S.; Cojocaru, C.S.; Pribat, D. Growth mechanisms of carbon nanostructures with branched carbon nanofibers synthesized by plasma-enhanced chemical vapour deposition. Cryst. Eng. Comm. 2014, 16, 2990-29995).
[0220]
[0160] Figure 12 shows TEM and HAADF elemental analysis of nanobelt carbon allotropes synthesized by molten carbonate electrolysis. Panel 1206 shows the elemental intensity profile taken along the white line to the left in bottom panel E, 1207 shows the HAADF data, 1208 shows the carbon content, 1209 shows the iron content, and 1210 shows the chromium content.
[0221]
[0161] Figure 13 shows TEM and HAADF elemental analysis of nanorod carbon allotropes synthesized by molten carbonate electrolysis. The top right panel shows the integrated atomic fraction over region #1 where the carbon content is about 90.6% and the oxygen is about 9.4%. The bottom right panel shows the integrated atomic fraction over region #1 where the carbon content is about 93% and the oxygen is about 7%.
[0222] Variations in the electrochemical conditions for CNT product formation relative to case #XVI result in an allotropic change from carbon nanotubes to another attractive morphology, referred to herein as nanodragons, and are presented in Table 3 and Figures 8 and 9B. Changes from the initial synthesis, which produced CNTs under similar conditions, include an Inconel 718 anode rather than Nichrome C, and a 0.1 A / cm 2 Instead, it has a higher current density of 0.4A / cm 2 (showing 100% coulombic efficiency) and the electrolyte was not aged. Unlike other unique electrolytically synthesized nanocarbon morphologies, carbon nanodragons are not composed of simple repeating geometric shapes; rather, nanodragons contain a complex combination of cylinders, platelets, and spheres. As shown in Figure 9B, nanodragons generally have an elongated body of CNTs with small "legs" or projections that extend away from the elongated body. The projections include smaller branched CNTs, small nodules of metallic growth, or any combination of these.
[0223] The addition of low levels of lithium oxide is known to have resulted in high quality CNTs. The use of a specific anode (Inconel 718 with two layers of Inconel 600) preserved the quality of the product but substantially altered the morphology of the CNTs. We have previously observed larger transition metal nodules growing from the CNTs. With the addition of Li2O, branched carbon nanotrees are included as electrolyte #XVII in Table 3 and Figure 8. The electrolyte was 0.13 A / cm 2The electrochemical run was run at 0.1 V and exhibits a Coulombic efficiency of 98.7%. The nanotrees show clear growth of smaller CNT branches emanating from a larger CNT trunk. The red circular area in the right panel of electrolysis #XVII in Figure 8 shows an example of a branched y-intercept. The addition of low levels of iron oxide results in high quality CNTs. However, upon aging of the electrolyte for 24 hours and subsequent additions as in Table 3 and electrolysis #XVIII in Figure 8, an alternative flattened nanocarbon allotrope was observed, referred to herein as a nanobelt. The electrolysis was run at 0.08 A / cm 2 and exhibits a Coulombic efficiency of 79%. The nanobelt structures appear to consist of flattened (or "shrunk") carbon nanotubes.
[0224]
[0164] TEM and HAADF elemental analyses of the nanoflower, nanodragon, nanobelt, and nanotree structures are presented in Figures 9A, 9B, 10, 12, and 13.
[0225]
[0165] Figure 9A shows the elemental composition by TEM and HAADF of the new nanoflower nanocarbon allotrope synthesized by molten carbonate electrolysis. As shown, the main components of the nanoflower are one or several interconnected tapered tubes containing bulbous sections at regular intervals. The walls consist of graphene layers as noted in Figure 9A and characterized by a typical graphene-wall separation of 0.33-0.34 nm as measured by the separation observed between dense TEM carbon planes. As seen in the HAADF image, the nanoflower contains not only Cu but also a small amount of cobalt.
[0226] In FIG. 9B, the nanodragon structure was seen as a graphitic structure, albeit complex. Structures with a similar appearance to Pt, but not C, have already been observed and described as a bumpy surface on one-dimensional Pt nanowires. The nanotree allotrope is shown in FIG. 10, which differs from conventional CNT structures that are composed of CNTs but do not generally contain fused CNTs. However, the nanotree morphology contains crossed CNTs as seen in FIG. 10, and the structure appears to be fused and branched with each other. A nanocarbon CVD growth branching mechanism has been suggested, catalyzed by a fraction of nucleation sites resulting in carbon branching, as shown in FIG. 11. In FIG. 10 and FIG. 12, it can be seen that the interior of the nanotrees and nanobelts can contain nickel and iron, or nickel, respectively, within the structure. As seen in FIG. 12, the nanobelt product is flat and composed of graphene layers besides the measured presence of nickel, and the mechanism of this unusual flat morphology was evident from TEM. CVD nanobelt CNT structures have already been synthesized with the schematic structure illustrated on the right side of FIG. 11.
[0227]
[0167] Without aging of the electrolyte (freshly melted electrolyte), low current density (0.08 A / cm 2, showing 80% Coulombic efficiency), long-term growth (18 hours) of carbon nanotube growth with a Monel cathode, iridium anode, 0.81% Ni, and a non-rising current activation step resulted in chunky ring-like nanorod allotropes as seen in Figure 13 and are included in Table 4 as Electrolysis XIX. Among the allotropes presented herein, the product was unusual from two physicochemical perspectives. First, the TEM in Figure 13 reveals no evidence of a layered graphene structure. However, as will be shown in a later section, this morphology exhibits XRD peaks and Raman spectra typical of a graphitic layered graphene structure. Second, as seen in the elemental analysis in Figure 13, the nanorods are the only new melt-synthesized nanocarbon structures, and significant concentrations of oxygen (7.0-9.4 wt%) were observed. The bulbous rod-like morphology, rather than the growth of an increasing length of the CNT along its diameter in time, seems consistent with long-term growth being dominated by an increase in diameter rather than length.
[0228] Example 4 Raman spectroscopy and XRD analysis of various nanocarbon allotropes
[0229] FIG. 14 shows SEM images of nanocarbon allotropes synthesized by electrolytic separation of CO2 in molten carbonate according to an embodiment of the present disclosure. Top and middle rows: nanocarbon allotropes introduced and synthesized according to an embodiment of the present disclosure. The bottom row shows nanocarbon allotropes already synthesized. Top row (from left to right) cone-shaped CNF (panel A), nanobamboo (panel B), nanopearl (panel C), Ni-coated CNT (panel D), nanoflower (panel F), and nanodragon (panel F). Middle row: nanorod (panel G), nanobelt (panel H), nanoonion (panel I), hollow nanoonion (panel J), and nanotree (panel K). Descending row (left to right): CNTs, nanoscaffolds (panel L, image from Wang, X., Licht, G.; Liu, X.; Licht, S. One pot facile transformation of CO2to an unusual 3-D nan-scaffold morphology of carbon. Sci Rep. 2020, 10, 21518), nanoplatelets, graphene (two-step process, image from Liu, X., Wang, X., Licht, G., & Licht, S. Transformation of the greenhouse gas carbon dioxide to graphene. J. CO2 Util., 36, 2020, 288-294), nanohelices (Liu, X.; Licht, G.; Licht, S. The green synthesis of exceptional braided, helical carbon nanotubes and nanospiral platelets made directly from CO2. Mat. Today Chem 2021, 22, (Image from 100529).
[0230]
[0170] Figure 15 shows Raman of CNM products consisting of various labeled nanocarbon allotropes and filled carbon nanotube assemblies synthesized by electrolytic separation of CO2 in Li2CO3 at 770°C with systematically varying electrochemical operating parameters. Table A below provides the reference numbers and associated characteristics utilized in Figures 165 16A and 16B.
[0231]
[0171] [Table 4]
[0232]
[0172] FIG. 16 shows XRD analysis of CNM products consisting of various nanocarbon allotropes synthesized by electrolytic separation of CO2 with Li2CO3 at 770° C. under various systematically varied electrochemical conditions.
[0233] The top and middle rows of Figure 14 compare microscopy of new carbon allotropes made according to embodiments of the present disclosure with structures in the second row already formed by melt electrolysis. The new electrochemically synthesized structures shown are cone-shaped CNFs, nanobamboos, nanopearls, Ni-coated CNTs, nanoflowers, nanodragons, nanorods, nanobelts, nanoonions (also previously synthesized by alternative methods), hollow nanoonions, and nanotrees. Previously well-defined nanocarbon structures synthesized were carbon nanotubes, nanoplatelets, graphene (two-step synthesis of CO2 melt electrolysis, and other exfoliations), and nanospirals.
[0234] FIG. 15 presents the effect of various electrolysis conditions on the Raman spectra and XRD of the new carbon products of CO2 electrolysis with Li2CO3 at 770 °C. The graphite fingerprint is observed at 1880–2300 cm -1 and is related to various collective vibrations of sp hybridized C-C bonds. The tangent G band (approx. 1580 cm -1 In) is E 2GIt is derived from a symmetric graphitic in-plane mode and can be split into several modes, two of which are the most distinct: G1 (1577 cm -1 ) and G2 (1610 cm -1 The Raman spectrum shows two sharp peaks at about 1350 and 1580 cm -1 These show disorder-induced modes (D band) and high-frequency E 2G Each corresponds to the first-order mode (G band) and has an additional peak, the 2D band, at 2700 cm -1 The G' peak at about 2300 appears to be related to the collective stretching vibration of the sp hybridized C-C bonds.
[0235]
[0175] In this specification, I D / I G The intensity ratio between the D and G bands (I D / I G ) is a useful parameter for assessing the relative number of defects and the degree of graphitization, and therefore I D / I G The ratio can be presented as a range of values (or as a specific numerical value) to distinguish one type of nanocarbon structure from another, such as the allotropes described herein. Table 4 summarizes the Raman band peak positions, calculated for various carbon allotropes (I D / I G ) and (I 2D / I G ) peak ratio. Higher ratio I D / I G , or I G The frequency shift is considered a measure of the defects that grow in the carbon graphitic structure. Possible defects in the graphitic structure include carbon sp , which is typical of the hexagonal carbon configuration in the graphene layers that comprise the structure. 2 Bond, sp 3 It is also contemplated that the substitution of 1,2-diphenyltetrahydrofuran (DPTA) with 1,2-diphenyltetrahydrofuran (DPTA) may be used to enhance defects in graphene, including increasing pores or missing carbon in the graphene and causing the formation of heptagons and pentagons rather than the traditional hexagonal graphene building blocks of graphene.
[0236]
[0176] [Table 5]
[0237]
[0177] Typically, I for multi-walled carbon nanotubes D / I G In comparison with these values, the new carbon allotropes produced according to the embodiments of the present disclosure, excluding the hollow nano-onions, generally have an I of 0.6 or less. D / I G The nanobamboos, nanopearls, nanorods, and nanobelts each exhibit relatively high levels of defects, which are often sp 3 This is associated with more pores and more twists and turns in the structure due to the higher presence of carbon. As can be seen from Table 4, the increasing I D / I G The order of the ratios is: CNT<Hollow Nano Onion<Dragon<Flower<Nano Tree<Bamboo<Pearl<Rod <CNF<ベルト It is.
[0238]
[0178] The shift in the frequency of the G band, ν, to higher frequencies is generally D / I G The shifts are correlated to the variations due to the ratios in the vicinity, with the exception of the unusually large shift observed for nanobamboo.
[0239]
[0179] High levels of Ni, Cr, or Co added to the electrolyte (nanobamboo, nanopearl, and nanoflower allotropes) also appear to correlate with increased defects, and the highly doped Ni powder used in nanorod synthesis showed increased defects in the I G Frequency shift and I D / I GThis correlates to very high levels of defects as indicated by an increase in the .Already, increasing concentrations of iron oxide added to the Li2CO3 electrolyte correlated to an increasing degree of disorder within the graphite structure.Interestingly, it is the synthesis with low levels of added iron oxide powder (but only added 24 hours before aging the electrolyte) that results in the allotrope with the highest level of defects, the nanobelt allotrope.
[0240]
[0180] Lower defects are relevant for applications requiring high conductivity and strength, while higher defects are relevant for applications enabling increased intercalation and higher diffusion rates through the structure, such as those associated with higher anode capacity in Li-ion batteries and higher charge supercapacitors.
[0241]
[0181] The XRD of the new nanocarbon allotrope products prepared according to embodiments of the present disclosure, along with an XRD library of related compound spectra, are presented in Figure 16 and summarized in Tables 2 and 3, and SEMs are presented in Figures 2, 7, and 8. Each of the spectra shows a strong, sharp diffraction peak at 2θ = 27° characteristic of a graphitic structure, with no indication of broad peaks indicative of amorphous carbon. In addition to graphite (carbon), the product XRD separates into groups where metal salts are present. Nanobamboo is characterized by the presence of lithiated nickel salts (lithium nickel oxide, Li2Ni8O 10 ) is present. The next most complex compositions are seen in Figure 18 for the nanodragon, hollow nanoonion, and nanotree allotropes, which contain iron carbide Fe3C, lithium nickel oxide, and carbon. In Figure 18, panel 1802 shows the elemental intensity analysis taken along the white arrow in panel D to the left. Panel 1804 shows the integrated atomic fractions over the area in the green box, which are approximately 94.3% carbon, 2.5% iron, and 3.2% nickel. In panel 1806, the integrated atomic fractions over the area in the green box are approximately 100% carbon. The next most complex compositions are shown in the lower left corner, which are seen to contain the previous metal salts (Li2Ni8O 10and Fe3C) and lithiated chromium (III) salts, respectively. Finally, it is noted that both the nanopearls and nanobelts contain an additional lithiated copper salt (lithium copper oxide, Li2CuO2), and that they were synthesized with Muntz brass and Monel cathodes, respectively, both of which contain copper. To enter the nanocarbon, copper may need to dissolve from the cathode, which was under cathodic bias. This did not occur with the other nanocarbon allotrope products of this disclosure. The nanobelt XRD spectrum is distinct from the others with a major peak at 2θ=43°, reflecting a much higher concentration of metal than in the other products. Li2Ni8O 10 The presence of reduced defects already described by Raman spectra for hollow nano-onion morphology, together with the presence of XRD for LiCrO2, LiCrO2, and Fe3C, provides evidence that the simultaneous presence of Ni, Cr, and Fe as nucleating agents can reduce defects in the structure compared to Ni. On the other hand, the presence of enhanced defects already described by Raman spectra for nanobelt and nanopearl morphology, together with the presence of XRD for LiCuO2, provides evidence that copper salts, as transition metal nucleating agents, increase defects in the structure compared to Ni, Fe, or Cr. Finally, it should be noted that the single (among all electrolysis) addition of cobalt powder to electrolytes XIV and XV must be correlated with the formation of the nanoflower allotrope observed thereafter. However, most of this cobalt does not go towards the product as analyzed by XRD in Figure 16, but is only observed in trace amounts by HAAFD TEM (to be revealed and probed in future studies), and probably has another role in promoting the formation of this unusual product.
[0242]
[0182] Without being bound by any particular theory, nanocarbon allotropes produced according to embodiments of the present disclosure may provide unusual physicochemical properties and suggest utility for applications, such as those that exploit the high strength, high thermal, magnetic, electrical, piezoelectric, and tribological properties of graphene-based materials, which are variously distributed throughout the unusual geometries of these novel allotropes. Alternative applications such as high capacity lithium anodes, unusual electronics, EMF shielding, improved lubricants, and new structural or polymer composites are contemplated.
[0243] Examples 1 through 4 describe nanocarbon allotropes made according to embodiments of the present disclosure and analyzed by SEM, TEM, TEM with HAADF, Raman, and XRD. With the exception of the nanorod structures, each of the structures was graphitic in nature, containing graphene layers arranged in various geometries. The graphene layers exhibit a characteristic interlayer spacing of 0.33-0.34 nm. Each of the structures was pure carbon, except for the presence of Ni, Fe, Cr, and sometimes Cu, which may act as nucleation growth sites. Generally, the intersecting graphene layers do not fuse, and in the nanotree allotropes, the graphene layers bend at the intersections, resulting in the branched structures observed.
[0244] Many of the structures, including nanobamboos, nanopearls, Ni-coated CNTs, and cone-shaped CNFs, show walls containing concentric graphene layers. Nanodragon and nanobelt structures contain layered planar or planar-twisted graphene layers. Some of the observed structures, including nanotrees, and hollow and filled nanoonions, show concentric highly spherical graphene layers that are generally composed of carbon and contain low levels of inner transition metals. Without being bound to any particular theory, embodiments of the present disclosure may provide a new synthetic route for the formation of nanoonions via the addition of phosphate to the electrolyte, which may be facilitated by the phosphate selectively binding transition metal ions.
[0245] All electrochemical methods proceeding from electrolysis #IV produce high purity products of the described allotropes, with the exception of small amounts (6%) of cone-shaped CNF in the majority of nanobamboo carbons and nanobelt carbon products of moderate purity (85%). The coulombic efficiency of the electrolysis is 0.08 A / cm. 2 At a lower current density of 0.2 A / cm, the 2 or higher current density. The high purity products have sharp XRD graphitic peaks and moderate (0.3–1.3) Raman I peaks indicating moderate levels of defects in the carbon structure, respectively. D / I G In addition to mostly pure graphitic carbon, XRD also showed a variety of single or mixed transition metal salts, either iron carbide, or nickel, chromium, or copper lithiated oxides.
[0246] TEM HAADF of the new nanocarbon allotropes showed that their inner cores were nearly metal-free (voids, 100% of the walls were carbon), but in other regions, the voids were filled with transition metals: Ni, Fe, and / or Cr. With the exception of the nanorod allotropes, each of the allotropes contained well-defined graphene layers with graphene characteristics, with interlayer spacings between 0.33 and 0.34 nm. Depending on the allotrope, adjacent graphene layers were organized into planar, cylindrical, or spherical geometries. When the inner transition metal was within the allotrope tip, the layered graphene walls are observed to bend to become highly spherical around the metal supporting a transition metal-nucleated CNT growth mechanism. The use of a nickel anode or excess nickel added to the electrolyte results in nickel-coated CNTs that are coated when stainless steel is used as the electrolytic cathode. Generally, the intersecting graphene layers did not fuse, but in nanotree allotropes with a trunk CNT and branch CNTs extending away from the trunk CNT, the graphene layers bent (or bent) to become part of the CNT intersections that coincide with the branches.
[0247]
[0187] Without being bound by any particular theory, molten carbonate electrolysis of CO2 provides an effective route to the synthesis of a portfolio of rare and valuable nanocarbon allotropes, as shown in Examples 1-4. Mass production of these allotropes from CO2 may provide a valuable incentive to consume this greenhouse gas. Such allotropes are rare or not previously existing, and are not generally commercially available. However, those in use, such as nano-onions - known to be made by pyrolysis of nanodiamonds or by CVD - have a high carbon footprint and associated costs of over $1 million / ton. CNT production by molten carbonate electrolysis of CO2 is a low-cost synthesis, comparable to the cost of aluminum oxide separation in the industrial production of aluminum. The new allotrope synthesis conditions consist of minor variations of the scaled molten carbonate electrolysis process, with a straightforward pathway comparable to that scaled up to contribute to CO2 consumption and climate change mitigation.
[0248] Example 5 Electrolysis operating parameters for producing CNM products with high CNT purity / yield
[0249] A further embodiment of the present disclosure relates to electrochemical process conditions that result in high purity, high yield CNT product by electrolysis of CO2 in lithium carbonate at 770°C. A detailed investigation of the product material composition and morphology was carried out, particularly around the transition metal nucleation zone of CNT growth. The latter part of the discovery reveals the melt electrochemical conditions that produce macroscopic assemblies of CNTs.
[0250]
[0190] Figure 17 shows SEM images of high purity, high yield CNM products of carbon nanotubes under various electrochemical conditions by electrolytic separation of CO2 in Li2CO3 at 770 °C. The washed products were collected from the cathode following electrolysis as described in Table 5. Moving from left to right in the panels, the products are analyzed by SEM at increasing magnifications. Scale bars in the panels (starting from the left) are: for panel A: 100, 50, and 10 μm; for panel B: 100, 20, and 5 μm; for panel C: 40, 5, and 2 μm; for panel E: 200, 40, and 10 μm.
[0251]
[0191] [Table 6]
[0252]
[0192] The electrochemical process conditions for high purity CNT synthesis were systematically varied to determine other electrochemical conditions that support high purity, low defect synthesis of straight (non-helical) CNTs. Examples of conditions varied are: cathode composition, anode composition, additives to lithium carbonate electrolyte, current density and electrolysis time. Electrode types include the use of cathode metal electrodes such as Muntz brass Monel or nickel alloys. Anode types include noble metal anodes, such as iridium, various nickel-containing anodes including nickel, nichrome A or C, Inconel 600, 625, or 718, or specific layered combinations of these metals. Electrolyte additives varied include Fe2O3, and nickel or chromium powder, and electrolysis was varied over a wide range of electrolysis current densities. Some electrolysis studies herein that resulted in high purity, high yield carbon nanotubes are described in Table 5. Scanning electron microscopy (SEM) of the products of various of these CNT syntheses as performed by CO2 electrolysis in molten Li2CO3 at 770 °C are presented in FIG.
[0253] For electrolysis #A, the top row of Table 5 presents the electrochemical conditions, and the top row of FIG. 17 presents the electrochemical conditions already described: 0.1 wt % Fe2O3 electrolysis (same lithium carbonate electrolyte, same Muntz brass cathode and Nichrome C anode, same 0.6 A / cm 2 We present SEMs of the products where the same electrochemical reaction rate (current density, and electrolysis duration of 30 minutes) is repeated but using a simpler (from a material standpoint) alumina (ceramic Al2O3) rather than stainless steel 304 electrolysis cell casing. The use of alumina casing in this discovery limits the pathways for metal to enter and reduces the parameters to evaluate or achieve the electrolysis system. Note, however, that stainless steel 304 was not observed to corrode and the switch from stainless to alumina was not observed to significantly affect the electrolysis product. The CNT product was again 97% pure, with a coulombic efficiency of 99%, which quantifies the available charge measured against the number of four electrons measured per equivalent of C in the product (current multiplied by electrolysis time), and the carbon nanotubes are 50-100 μm in length.
[0254] In the second row of FIG. 17 (Panel #B), the current density is changed to 0.15 A / cm 2 and the electrolysis time is increased to 4 h. The result of these modifications is a decrease in product purity to 94%, a decrease in CNT length to 20-80 μm, and a moderate decrease in Coulombic efficiency to 98%. At this current density, the addition of 0.1 wt% Ni together with 0.1 wt% Fe2O3 results in non-straight, zigzag, twisted CNTs of 96% purity, as observed in Figure 2, row 3, panel #C. These twists may be induced by over-nucleation reducing control of CNT linear growth. In the most magnified of these product images (right side of Figure 17, 2 μm scale bar resolution), evidence of over-nucleation is observed in the even larger nodules seen at the tips and junctions of the CNTs.
[0255]
[0195] 0.08A / cm 2At low current densities of 10 ... 2 The bottom row (panel #E) of Figure 17 shows that the product was highly pure (97%) and consisted of CNTs with lengths of 20-50 μm, with a coulombic efficiency of 75%. Although not shown, Table 5 (Electrolysis #G) also shows that the same CNTs were produced under the same electrodes and at the same 0.08 A / cm 2 Electrolytic conditions are included. However, J=0.15A / cm 2 With both electrolyte additions of 0.1 wt % Fe2O3 and 0.1 wt % Ni, the product is twisted CNTs as shown in Figure 17 panel #17 with a purity of 96% and a coulombic efficiency of 80%.
[0256]
[0196] Figure 18 shows TEM and HAADF of high purity, high yield CNT CNM products under electrochemical conditions #E (Table 5) by electrolytic separation of CO2 with Li2CO3 at 770 °C. In the top row, products are analyzed by TEM with scale bars of 20 nm (left panel) or 1 nm (right). Moving from left to right in the second row, there are scale bars of 100, 5, 5, and 1 nm. In the third row, the scale bars are 100 or 50 nm. In the bottom row, the scale bars are 20, 1, and 1 nm.
[0257] The syntheses listed in Table 5 define electrochemical growth conditions for high purity growth of carbon nanotubes, each exhibiting the characteristic concentric multi-layer graphene cylindrical walls. This is observed in Figure 18, which presents TEM and HAADF of a typical example (product of electrolysis #E as further described in Table 5 and Figure 17) and provides schematic structural and mechanistic information of carbon nanotubes synthesized by melt electrolysis. As seen in the top row of the figure, the carbon nanotubes are formed by successive concentric layers of cylindrical graphene. The graphene is identified by its characteristic graphene interlayer separation of 0.33-0.34 nm, measured in the figure by the spacing between the dark layers of uniform block electron transmission in the magnified upper right side of the figure. This CNT has an outer diameter of 74 nm and an inner diameter of 46 nm, and by counting the dark rows, the number of graphene layers of this CNT is determined to be 41. The right side of the third row of Figure 18 shows the measurement of the carbon elemental profile of the CNT. The profile is swept laterally from the outside of the tube (no carbon) by going through the left wall (carbon), then through the void inside the tube (low carbon from the outside back wall), then through the right wall (carbon) and finally to the outside of the tube on the outside left side (no carbon).Similarly, the integrated elemental profile for region 1 of this panel is shown, showing 100.0% carbon (fit error 1.3%).
[0258]
[0198] On the right side of the second row of Figure 18, the parallel 0.34 nm spacing for the graphene layers of the CNT wall is again observed. This panel also contains dark areas of metal trapped within the CNT, serving as a snapshot of the growth of the CNT over time. In the third row of Figure 18, the HAADF analysis of region #1 has an elemental composition for this region, including the wall, where the trapped internal metal is 94.4% carbon, 2.5% Fe, and 3.2% Ni, distributed according to the individual C, Fe, and Ni HAADF maps included in Figure 18. The second row of Figure 18 also shows the tip of the CNT containing the trapped metal. The transition metal acts as a nucleating agent, supporting the formation of the curved graphene layers shown at the tip of the CNT, which is a major component of the CNT growth mechanism. Although occurring in an entirely different physicochemical environment than chemical vapor deposition (CVD), this molten carbonate electrolysis process of transition metal nucleated grown CNT appears similar to that described as occurring in CVD CNT growth. This is despite the fact that CVD is a non-chemical / non-electrochemical process, occurring at a gas / solid interface rather than a liquid / solid interface.
[0259] Example 6 Electrochemical operating parameters for producing CNM products with high aspect ratio CNTs
[0260]
[0200] Figure 19 shows SEM images of CNM products of high aspect ratio (and high purity and yield) CNTs from electrolysis #F in Table 5, separating CO2 with 770 °C Li2CO3, according to an embodiment of the present disclosure. From left to right in the panels of Figure 19, the products are analyzed by SEM at increasing magnifications. Scale bars (clockwise from top) for panels Fa-Ff are 500, 400, 100, 5, 5, and 10 μm.
[0261] FIG. 19 shows an SEM image of the product of the electrochemical configuration that yields the longest (100-500 μm long) and highest purity (98%) CNTs with the highest coulombic efficiency (99.5%) of those studied here (denoted as Electrolysis #F in Table 5). As in the previous configuration, it yields nearly as high purity but shorter CNTs. The synthesis used 0.1 wt% Fe2O3 additive in Li2CO3 electrolyte, a Muntz brass cathode, and an Inconel 718 anode with a layered Inconel 600 screen. However, this synthesis used two layers of Inconel 600 instead of three, as well as a higher current density (0.08 A / cm2). 2 Instead of 0.4A / cm 2 ) and shorter electrolysis times (4 hours instead of 15 hours) were used to find optimization of CNT purity and length. With a diameter of <0.2 μm, these CNTs can have aspect ratios >1,000. As correlated to the alloy composition in Table 5, the smaller number of Inconel 600 layers reflects the potential need to encompass the available anodic molybdenum in the alloy, but at controlled lower concentrations, high purity, high aspect ratio CNTs are achieved. As shown in FIG. 19, the CNTs are close packed and parallel to a large extent, and may include useful candidates for use in nanofiltration as discussed herein.
[0262] FIG. 20 shows TEM and HAADF analysis of CNM products of high purity, high yield CNTs under electrochemical conditions of electrolysis #F (Table 5) by electrolytic separation of CO2 in Li2CO3 at 770° C. In the top row, the products are analyzed by TEM with a scale bar of 1 μm (left panel) or 100 nm (right). From left to right, the scale bar in the middle right has a scale bar of 50, 20, and 1 nm. Each HAADF measurement in the bottom panel has a scale bar of 200 nm. Panel 2002 shows elemental intensity data obtained along the white arrow shown in the panel to the left. Panel 2004 shows the integrated atomic fraction data in the green box, where carbon is essentially 100%. Panel 2006 shows the integrated atomic fraction data obtained from the green box (with white arrow inside) where carbon is about 92.9%, iron is about 6.8%, and nickel is about 0.3%.
[0263]
[0203] Figure 20 shows TEM and HAADF analysis of the high aspect ratio CNT product of electrolysis #F (as described in Table 5 and by SEM in Figure 19). As seen in the right side of the middle row of Figure 20, the CNT walls consist of parallel carbon layers separated by the characteristic 0.33-0.24 nm graphene layer spacing. As seen in the elemental analysis of region #1 in the bottom row, the region consists of a hollow tube composed of 100% carbon. However, there are also extensive portions of the tube intermittently filled with metal, as seen in the TEM of the top two rows and the bottom row of HAADF elemental profiles. In the bottom row of Figure 20, a side cross-sectional elemental CNT profile scanned from the outside through region #2, through the CNT, and then out the opposite wall shows that the walls are composed of carbon, while the interior region also contains iron as the major metal present along with some nickel.
[0264] Example 7 Electrochemical operating parameters for preparing CNM products as thin CNT allotropes
[0265]
[0205] Figure 21 shows SEM images of CNM products of high purity, high yield CNTs under various electrochemical conditions by electrolytic separation of CO2 in Li2CO3 at 770 °C. The washed products are collected from the cathode following electrolysis as described in Table 5. Scale bars (starting from the left) are: for panel J: 100, 4, and 2 μm; for panel I: 100, 10, and 4 μm; for panel K: 40, 5, and 3 μm; for panel L: 40, 50, and 5 μm.
[0266]
[0206] Figure 22 shows TEM and HAADF of CNM products of carbon nanotubes showing nodules or buds under electrochemical conditions of electrolysis #H (Table 5, and SEM in top row of Figure 22) by electrolytic separation of CO2 in Li2CO3 at 770°C. In the top row of Figure 22, the products are analyzed at scale bars from left to right of 200, 100, 20, and 100 nm. The second row has a scale bar of 1 μm, then 20, 5, 200, and 1 nm. The third row has scale bars of 200, 20, 1, 5, and 200 nm. The bottom row has scale bars of 50, 1, 1, and 200 nm.
[0267]
[0207] Figure 21 demonstrates that additional modification of electrolysis conditions can result in high purity carbon nanotubes by CO2 melt electrolysis. In the top row, panel #H, as in the high current density case (Figure 17, panel #A), a moderate current density of 0.4 A / cm 2 (The same electrolyte, Muntz brass cathode, and Nichrome C anode result in longer (100-200 μm), higher purity (96%) CNTs with coulombic efficiency approaching 100%. In the second row (FIG. 21, panel A), switching the cathode material to Monel results in shorter 20-50 μm CNTs with 97% purity and also with coulombic efficiency approaching 100%. Although not shown, Table 5 (Electrolyte #D) also shows that switching from Nichrome C to a pure nickel anode (while retaining the Monel cathode, and electrolyte additive at J=0.2 A / cm) 2) results in a substantial drop in CNT purity to 70%, with the remainder of the product consisting of nano-onions. 2 A drop in current density to 1000 Å results in 97% pure CNTs of 30-60 μm in length with only a slight drop in coulombic efficiency to 97%. In a single panel #L located in the lower left corner of Figure 21, excess Fe2O3 is added, which is already observed to lose control of the specificity of the synthesis. In this case, the total purity of CNTs remains high at about 95%, but this consists of two clearly different morphologies of CNTs in the product. The majority product of about 75% is twisted CNTs, and the minority product of about 20% is straight CNTs. Finally, in panel #M in the middle and right bottom row of Figure 21, a noble metal, iridium, is used as the anode (with a Monel cathode) at a low current of 0.08 A / cm. 2 current density. The transition metal released from the anode can contribute transition metal ions reduced at the cathode during the formation of its stable oxide overlayer and can act as nucleation points for the CNTs. This cannot be said here due to the high stability of iridium. Instead, a single high-concentration transition metal, 0.81 wt. % Cr, is prepared as an electrolyte additive. The product is the thinnest (<50 nm diameter), highly pure (97%) CNTs shown, 50-100 μm long for an aspect ratio >1,000, and formed with 80% Coulombic efficiency.
[0268]
[0208] SEMs of some CNM products, especially electrolytic #H, #B, and #C, show evidence of nodules that appear to be "buds" attached to the CNTs. This nanobud allotrope is most consistent in electrolytic #H and is further explored by TEM and HAADF in Figure 22. As seen in the top row of Figure 22, the nanobuds generally have a spherical symmetry extending away from the longitudinal axis of the CNT, and although there is no spreading in this structure, the nanobuds appear to be comparable to a bunch of grapes growing on a vine. The nanobuds generally contain low levels of transition metal nucleating metal, e.g., 0.3% Fe is evident, and the remainder of the structure is generally pure carbon that may occasionally contain a metal core. As seen on the left side of the second row, the CNT walls continue to show regular 0.33-0.34 graphene wall-to-wall separations, as seen on the right side of the row, and the junctions of adjacent CNTs may have fused or entirely different graphene structures. Similarly, adjacent nanobuds on a CNT can have graphene walls that bend and are shared to join, as seen in the third row of Figure 17, or that instead appear to be distinctly different (entangled, not fused) structures, as seen in the fourth row.
[0269] Example 8 Electrochemical operating parameters for producing CNM products with macroscopic assemblies of nanocarbon allotropes
[0270] In addition to synthesizing individual CNTs, this Example 8 provides a series of electrolysis to generate useful macroscopic assemblies of CNTs.There is growing interest in close-packed CNTs for nanofiltration, and also due to their high density of conductive wires as artificial neural nets.The macroscopic assemblies produced by the embodiments of the present disclosure are referred to as nanosponge, close-packed parallel CNTs, and nanoweb CNTs in Table 6 and Figure 23.
[0271]
[0211] [Table 7]
[0272] FIG. 23 shows SEM images of CNM products consisting of carbon nanotubes arranged in various packed macroscopic structures, also referred to as macroassemblies herein, amenable to various applications including nanofiltration. The washed products are collected from the cathode following electrolysis as described in Table 6. From left to right in the panels, the products are analyzed by SEM at increasing magnification. Identified allotropic components include nanosponge, close-packed linear CNTs, and nanoweb CNTs. From left to right in the panels, the products are analyzed by SEM at increasing magnification. The scale bars in the panels (starting from the left) are: for panel N: 500, 40, and 20, and 8 μm; for panel P: 400, 10, and 5 μm; for panel d: 300, 40, and 5 μm; for panel Q: 500 μm 40, 20, and 8 μm.
[0273] The nanosponge allotrope was tested at 770° C. when Nichrome C acted as both the cathode and anode and 0.81% Ni powder was added to the Li2CO3 electrolyte and the initial current increased upwards (0.008, 0.016, 0.033, and 0.067 A / cm 2 at 0.2 A / cm for 5 min each, then 4 h at 0.2 A / cm 2 Nanosponges of 97% purity were formed with 99% Coulombic efficiency by electrolysis #N, with a current density of 0.15 A / cm2. As previously described, long, close-packed parallel carbon nanotubes were prepared by electrolysis #F, using 0.1 wt% Fe2O3 in a Li2CO3 electrolyte, a Muntz brass cathode, and an Inconel 718 anode, with two layers of Inconel 600 screens. 2In contrast to the parallel assemblies produced with electrolysis #F, nanowebs properly describe the interwoven carbon nanotubes from electrolysis #P and #Q, presented in the bottom row of Table 6 and in Figure 23. Two different routes to nanoweb assembly are summarized. The first was a 0.1% Fe2O3 additive, Muntz brass cathode, and Inconel 718 anode with three layers of Inconel 600 screen at 0.08 A / cm 2 The second route uses approximately 0.81 wt% Ni powder additive, a Monel cathode, and a Nichrome C anode at 0.28 A / cm to generate 97% pure nanowebs with a coulombic efficiency of 79%. 2 to generate nanowebs of 92% purity with a coulombic efficiency of 93%.
[0274]
[0214] Densely packed, straight CNTs define inter-CNT spacings ranging from 50 to 300 nm, and the CNTs are also highly aligned and can be said to be substantially parallel to one another, providing unusual nanofiltration opportunities, both in domains of this size and in 1D filtering from 3D morphologies. Nanosponges lack this alignment feature, and from Figure 23 it can be seen that nanosponges define nanofiltration pores ranging in size from about 100 to about 500 nm, while the nanoweb allotrope provides nanofiltration with pore sizes from about 200 nm to about 1 μm.
[0275] Example 9 Raman Spectroscopic and XRD Characterization of the CNM Products of Examples 5-8
[0276] FIG. 24 shows Raman spectroscopy analysis of CNM products consisting of various labeled CNT assemblies synthesized by electrolytic separation of CO 2 in Li 2 CO 3 at 770° C. under various systematically varied electrochemical conditions as described in Table 7.
[0277]
[0217] [Table 8]
[0278] FIG. 25 shows XRD analysis of CNM products consisting of various labeled CNT assemblies synthesized by electrolytic separation of CO2 in Li2CO3 at 770° C. under various systematically varied electrochemical conditions described in Table 7.
[0279] FIG. 24 presents the Raman spectral effect of varying CNT electrolysis conditions on the CNT assembly products from CO2 electrolysis in Li2CO3 at 770 °C. The Raman spectra show disorder-induced modes (D band) and high frequency E 2G Two sharp peaks at approximately 1350 and 1580 cm, respectively, corresponding to the first-order mode (G band) -1 and an additional peak, the 2D band, at 2700 cm -1 In the spectrum, the graphite fingerprint is shown at 1880-2300 cm -1 and are related to various collective vibrations of sp hybridized C-C bonds.
[0280]
[0220] Interpretation of the Raman spectra provides insight into the potential applications of various carbon allotropes. From FIG. 24, the intensity ratio between the D and G bands (I D / I G ) is calculated or observed I G The shift in frequency is a useful parameter to assess the relative number of defects and the degree of graphitization is presented in Table 7. In particular, for the nanosponge, nanoweb, and close-packed linear CNT assemblies shown in FIG. 23, the nanoweb CNT assemblies are ranked I in Table 7. D / I G = 0.36, and the close-packed CNT assemblies exhibit a low degree of disorder, I D / I G = 0.49, and the nanosponge exhibits an intermediate degree of disorder, I D / I G = 0.62, which shows the highest degree of disorder. G Note that this is accompanied by a shift in frequency.
[0281]
[0221] I D / I G For assemblies with increasing ratio: CNT nanoweb <densely packed CNT <CNTナノスポンジ It is.
[0282] It has been previously demonstrated that increasing concentrations of iron oxide added to the Li2CO3 electrolyte correlate with increasing degrees of disorder within the graphite structure. D / I G It should be noted that the lattice defects remain relatively low, as reported for multi-walled carbon nanotubes made by other synthetic processes at >1. Lower defects are associated with applications requiring high electrical and strength, while higher defects are associated with applications that allow high diffusivity through the structure, such as those associated with increased intercalation and higher anode capacity in Li-ion batteries and higher charge supercapacitors.
[0283] XRD along with an XRD library of related compound spectra are presented in FIG. 25 for the CNT assembly products prepared as shown in FIG. 23 and Table 6. Each of the spectra shows a strong diffraction peak at 2θ=27°, characteristic of a graphitic structure. The nanosponge XRD spectrum is distinct from the others with a major peak at 2θ=43°, and the match of the XRD spectra indicates that Li2Ni8O 10 The nanosponge XRD shows the presence of nickel as Li2Ni8O and chromium as LiCrO2. The nanosponge XRD shows little to no iron carbide. On the other hand, both the nanoweb and the close-packed linear CNTs show additional significant peaks at 2θ = 42 and 44°, which are indicative of the presence of iron carbide, Fe3C. Li2Ni8O 10The reduced presence of defects previously noted by Raman spectra for other close-packed CNTs, along with the presence of XRD of LiCrO2, LiCrO2, and Fe3C, provides evidence that the simultaneous presence of Ni, Cr, and Fe as nucleating agents can reduce defects in the CNT structure compared to Ni and Cr alone.
[0284] Example 10 Scale-up electrolytic operating parameters to produce CNM products with desired nanocarbon allotropes of high purity
[0285] This example demonstrates that various nanocarbon allotropes can be electrosynthesized in high purity and high yield using larger electrodes and simpler modified conditions. Each of the three cases used in this Example 10 generates three different and highly pure allotropic products: (i) CNTs; (ii) carbon nano-onions; or (iii) carbon nanopearls, using similar electrolysis operating parameters, but using different anode geometries as well as different electrolysis current densities, each of which can affect which metals enter the electrolyte. Each of the three electrosyntheses was performed on a 39 cm high by 34.5 cm wide (approximately 1,345.5 cm) electrode per face. 2 The electrolysis was carried out in a molten Li2CO3 electrolyte at 750 °C containing a Muntz brass cathode with a bifacial active surface area of 1.0 nm (having a surface area of 1.0 nm). The cathode was sandwiched between stainless steel 304 anodes. In the first two cases (i) and (ii), the electrolysis was carried out at approximately 0.2 A / cm with an inlet of 98% CO2 at 1.9 L / min. 2 and the third case (iii) was run at a constant current density of 0.8 L / min with a CO inlet of approximately 0.07 A / cm 2In addition to the current density, a further difference between the three cases was the geometry of the stainless steel anodes that sandwiched either side of the cathode. In the first case (i), the anode was a solid steel plate, generating a product with high purity CNT allotropes. After washing to remove excess electrolyte, the TGA and TGA derivatives of the product are shown in Figure 26, while an SEM image at increased magnification can be seen in the bottom panel of Figure 27. As seen in the TGA, the product had a low retention of 6.7% and a high T inflection =596.9°C, indicating a highly graphitic (resistant to oxidation) structure, while SEM images reveal high purity carbon nanotube morphology of the product. The actual sample purity is lower than the TGA residue of 6.7%; the 6.7% is the oxidized (consumed) mass of (metal) residue. Higher carbon nanotube TGA purity for carbon nanotubes was obtained by also increasing the anode to cathode spacing (i.e., interelectrode space) from about 2.5 cm (1") to about 10 cm (4"), at about 0.2 A / cm. 2 At a constant current density of 0.2 A / cm, a retention rate of about 4% is achieved when using a larger electrode with a width of 36 inches (91.14 cm). 2 At a current density of 1000 nm, the current applied to the electrodes is several thousand amps. Results are reproducible with CO2 captured directly from air and with CO2 from the exhaust gases of a natural gas power plant. The larger spacing accommodated a longer deposition time of 16 hours, resulting in a thicker deposition of approximately 3.5" from each side of the sandwiched cathode. Without wishing to be bound by any theory, the inventors hypothesize that the larger accommodating CNT growth requires less additional nucleating metal, which results in the observed increase in TGA purity (lower observed TGA residual relative mass).
[0286] In the second case (ii), the anode was a new steel (tatami weave) screen, which generated a high purity carbon nano-onion product, as seen in FIG. 28. In addition, a new (fresh) stainless steel 304 electrolysis case was utilized. The fresh electrolysis case tends to be activated to produce high purity carbon nanotubes following the first electrolysis run. After washing to remove excess electrolyte, the TGA and TGA differential of the product are shown in FIG. 28, while the SEM image at increased magnification is shown in FIG. 29. As seen in FIG. 28, the product had a low retention rate of about 4.01% and a high T inflection = 542.8°C. These results show a graphitic (resistant to oxidation) structure, while SEM images reveal the product steel-purity carbon nano-onion allotrope. In this case, repeated subsequent electrolysis with this anode generates high-purity carbon nanotube product. This subsequent carbon nanotube formation is due to improved anodic release of transition metals to nucleate carbon nanotube formation compared to the new electrolysis case and anode configuration. Without wishing to be bound by any theory, this carbon nano-onion formation is due to suppressed release of transition metals from the mesh electrode and from the new steel case to nucleate carbon nanotube formation compared to using the new electrolysis case and desired anode configuration.
[0287]
[0227] The melting point of Li2CO3 is 723°C. Another means observed to generate carbon nano-onions - instead of using a screen, a simpler flat stainless steel anode is used, which has been found to be more effective in both the first and subsequent electrolysis, starting the electrolysis at a lower temperature where the electrolyte is only partially melted. This also forms highly pure carbon nano-onion products. For example, in repeated experimental runs of electrolysis reactions, CNM products with carbon nano-onions have demonstrated TGA retention rates of 5.3% and 7.4%. Without wishing to be bound by any theory, this carbon nano-onion formation follows another example of the inhibited formation of nucleation sites on the cathode, which inhibits carbon nanotube formation and favors highly pure carbon nano-onion formation.
[0288] In the third case (iii), the anode was a perforated steel sheet. After washing to remove excess electrolyte, the TGA and TGA differential of the product are shown in Figure 30, while the SEM image at increased magnification is shown in Figure 31. As can be seen in Figure 30, the product had a moderate retention rate of 15.1%, indicating a higher metal content in the product, and a high T inflection = 597.7° indicates a graphitic (resistant to oxidation) structure, while SEM reveals a high purity carbon nano-onion morphology of the product. Without being bound by any theory, this carbon nanopearl product formation may be induced by a higher metal content in the product, which may be related to the enhanced metal release from the perforated sheet anode configuration.
Claims
1. 1. A method for producing a carbon nanomaterial (CNM) product, comprising: (a) heating an electrolyte medium to obtain a molten electrolyte medium; (b) positioning the molten electrolyte medium between a high nickel content anode and a cathode of an electrolytic cell; (c) introducing a source of carbon into the electrolysis cell; (d) applying an electrical current to the cathode and the anode of the electrolytic cell; (e) collecting the CNM product from the cathode; wherein the CNM product comprises a minimum relative amount of a desired allotrope selected from the group of conical carbon nanofibers, nanobamboos, and nanotrees of at least 70% by weight compared to the total weight of the CNM product, the nanotrees comprising a trunk carbon nanotube (CNT) having multiple branch CNTs extending away from the trunk CNT, and the high nickel content anode is made of pure nickel or an alloy comprising greater than 50% by weight nickel.
2. The method of claim 1 further comprising the step of adding an iron-containing salt to the electrolyte medium or the molten electrolyte medium.
3. The method of claim 1, wherein the high nickel content anode comprises an alloy containing at least 50% nickel by weight.
4. The method of claim 1, wherein the high nickel content anode is a composite anode comprising a first layer of a first alloy containing at least 50% by weight nickel and a second layer of a second alloy containing at least 50% by weight nickel, the first alloy and the second alloy being different.
5. 10. The method of claim 1, wherein the anode and the cathode are both made of pure nickel and the desired allotrope is nanobamboo.
6. 2. The method of claim 1, further comprising adding a nickel-containing additive to the electrolyte medium or the molten electrolyte medium relative to an amount of the electrolyte medium or the molten electrolyte medium, wherein the anode is a composite anode comprising a first layer of a first alloy comprising at least 50% by weight nickel and a second layer of a second alloy comprising at least 50% by weight nickel, wherein the first alloy and the second alloy are different, and the desired allotrope is nano-bamboo.
7. The method of claim 1 , wherein the molten electrolyte medium is freshly melted and the CNM product comprises cone-shaped nanofibers.
8. 2. The method of claim 1, further comprising adding a nickel-containing additive to the electrolyte medium or the molten electrolyte medium, wherein the anode is a composite anode comprising a first layer of a first alloy comprising at least 50% by weight nickel and a second layer of a second alloy comprising at least 50% by weight nickel, wherein the first alloy and the second alloy are different, and the desired allotrope is nano-bamboo.
9. 10. The method of claim 1, further comprising introducing a lithium-containing additive into the electrolyte medium or the molten electrolyte medium, wherein the anode is a composite anode comprising a first layer of a first alloy comprising at least 50% by weight nickel and a second layer of a second alloy comprising at least 50% by weight nickel, wherein the first alloy and the second alloy are different, and the desired allotrope is a nanotree.
10. 10. The method of claim 9, wherein the lithium-containing additive is lithium oxide and is added in an amount between about 0.05% and 0.5% by weight relative to the amount of the electrolyte medium or the molten electrolyte medium.
11. 10. The method of claim 1, further comprising the step of introducing a magnetic additive component into the electrolytic cell, the magnetic additive component comprising a magnetic material addition component, a carbide growth component, or any combination thereof, and wherein the desired allotrope is magnetic and moves when in a magnetic field.
12. 10. The method of claim 1, further comprising the step of introducing a doped additive component into the electrolytic cell, wherein the desired allotrope is doped and atoms of the doped additive component are incorporated directly throughout the doped desired allotrope to impart desired physical and / or chemical properties to the doped desired allotrope that differ from an undoped desired allotrope.